5G as Enabler for Industrie 4.0 Use Cases: Challenges and Concepts - Gundall, Michael; Schneider, Jorg; Schotten, Hans D.; Aleksy, Markus; Schulz, Dirk; Franchi, Norman; Schwarzenberg, Nick; Markwart, Christian; Halfmann, Rudiger; Rost, Peter; Wubben, Dirk; Neumann, Arne; et al. (IEEE International Conference on Emerging Technologies and Factory Automation, ETFA, 2018)
The increasing demand for highly customized products, as well as flexible production lines, can be seen as trigger for the 'fourth industrial revolution', referred to as 'Industrie 4.0'. Current systems usually rely on wire-line technologies to connect sensors and actuators. To enable a higher flexibility such as moving robots or drones, these connections need to be replaced by wireless technologies in the future. Furthermore, this facilitates the renewal of brownfield deployments to address Industrie 4.0 requirements. This paper proposes representative use cases, which have been examined in the German Tactile Internet 4.0 (TACNET 4.0) research project. In order to analyze these use cases, this paper identifies the main challenges and requirements of communication networks in Industrie 4.0 and discusses the applicability of 5th generation wireless communication systems (5G).
CRIS-Team Scopus Importer:2021-06-08
Keywords: 5G; industrial communication; Industrie 4.0; KPI; TACNET 4.0

5G netmobil: Pathways towards tactile connected driving - Hofmann, Frank; Franchi, Norman; Fettweis, Gerhard; Mahdi, Ali H.; Brahmi, Nadia; Wegmann, Bernhard; Muehleisen, MacIej; Petry, Florian; Mudriievskyi, Stanislav; El Assaad, Ahmad; Jornod, Guillaume (IEEE 5G World Forum, 5GWF 2019 - Conference Proceedings, 2019)
Vehicular communications is not only a major opportunity to improve road safety and traffic efficiency but also a key enabler for connected and automated driving. The analysis of future automotive applications and their needs performed in the project 5G NetMobil has brought up various technical challenges that need to be solved in order to support advanced use cases such as High Density Truck Platooning. In this regard, we provide a description of several technical solutions developed within the project to respond to these arising communications demands in terms of reliability and latency. This includes a holistic E2E architecture comprising the concept of hybrid communications to achieve stringent reliability requirements, concepts for monitoring and controlling of QoS as well as network slicing and agile edge cloud concepts to shift parts of the vehicular functionality into the cloud. In addition to an overview of the activities within 5G NetMobil, this paper gives first interim results and insights.
CRIS-Team Scopus Importer:2021-06-08
Keywords: 5G; 5G NetMobil; C-ITS; V2X; Vehicular communications

A 150-168 GHz Mixer and Quadrupler Unit in SiGe BiCMOS Technology for JCAS Applications Based on DDS Signal Generation Up to 5 GHz - Isbilen, Timur; Breun, Sascha; Arneth, Nils; Schrotz, Albert-Marcel; Scheller, Kai; Franchi, Norman; Weigel, Robert (2025 IEEE Wireless and Microwave Technology Conference (WAMICON), 2025)
This paper presents a fully integrated mixer and quadrupler unit with a 3 dB bandwidth from 150 to 168 GHz and a maximum output power of -15 dBm. The circuit is designed for JCAS applications focusing on the up-conversion of arbitrary ramp sequences (e.g., for FMCW radar) generated by a commercial DDS block. The unit comprises a polyphase filter, LO buffer amplifiers, a double-balanced single-sideband mixer, and a subsequent frequency quadrupler, which provides a bandwidth extension by a factor of four. Thus, 18 GHz of bandwidth in the D-band can be achieved by using a 4.5 GHz DDS signal source. The proposed arrangement is optimized for low phase noise, high spurious-free dynamic range (SFDR), and compatibility with various communication applications. An SFDR exceeding 24dBc is maintained across the entire measured RF frequency range (150 to 168 GHz), with suppression of spurs greater than 30 dBc observed in the 156 to 164 GHz range. The circuit was fabricated using a 90 nm SiGe BiCMOS technology with ft/fmax of 300GHz/500GHz, respectively, and has a power consumption of 175 m
Keywords: direct digital synthesis; FMCW radar; D-band; joint communication and sensing; single-sideband mixer; frequency quadrupler; SiGe BiCMOS

A 21 GHz Bandwidth 30 dB Gain VGA for 6G Basband Systems in 22 nm FDSOI - Hetterle, Philip; Engelmann, Andre; Scheller, Kai; Huang, Tianzhu; Weigel, Robert; Franchi, Norman (German Microwave Conference (GEMIC), 2025)
This paper presents a 5-stage wideband variable gain amplifier (VGA) integrated in 22 nm fully-depleted silicon-on-insulator (FDSOI) CMOS technology. The circuit comprises three different core circuit topologies, composed by an input buffer, three gain control stages and a high-power ouput stage. The VGA achieves 30 dB gain with a power consumption of 44 mW, exhibiting a continuous tuning range of 33 dB, covering a 3 dB bandwidth of 21 GHz, while occupying a area of 0.077 mm2. The VGA is optimized for operation within high-data rate 6G receiver system
Keywords: CMOS; FDSOI; VGA; baseband; low voltage; mobile communication; IC; 6G.

A 304 to 337 GHz Push-Push Frequency Doubler with 6.8 dBm Pmax using T-Junction Combining in 90 nm SiGe BiCMOS Technology - Breun, Sascha; Schrotz, Albert-Marcel; Koch, Manuel; Franchi, Norman; Weigel, Robert (German Microwave Conference 2025, 2025)

Accelerating Deep Learning in Radar Systems: A Simulation Framework for 60 GHz Indoor Radar - Reitz, Philipp; Maiwald, Timo; Bönsch, Jonas; Franchi, Norman; Lübke, Maximilian (Remote Sensing, 2024)
FMCW radar systems are increasingly used in diverse applications, and emerging technologies like JCAS offer new opportunities. However, machine learning for radar faces challenges due to limited application-specific datasets, often requiring advanced simulations to supplement real-world data. This paper presents a setup for generating synthetic radar data for indoor environments, evaluated using CNNs. The setup involves comprehensive modeling, including far-field antenna simulations, variations in human radar cross-section, and detailed representations of indoor environments with their corresponding propagation channel properties. These synthetic data are used to train CNNs, and their performance is assessed on real measurement data. The results demonstrate that CNNs trained on synthetic data can perform well when tested on real measurement data. Specifically, the models trained with synthetic data showed performance comparable to models trained with real measurement data, which required a minimum of 300 samples to reach similar levels of accuracy. This result demonstrates that synthetic data can effectively train neural networks, providing an alternative to real measurement data, particularly when collecting sufficient real-world samples is difficult or costly. This approach significantly reduces the time required for generating datasets, and the ability to quickly label data in simulations simplifies and accelerates post-processing. Additionally, the generated datasets can be made more heterogeneous by introducing varying signal conditions, enhancing the diversity and robustness of the training dat
Keywords: convolutional neural network; FMCW radar; mm-wave; radar cross section; simulation and measurement

A code-orthogonal PMCW transmission scheme for improving communications performance in JCAS systems - Su, Yanpeng; Shatov, Victor; Franchi, Norman; Lübke, Maximilian (IEEE Access, 2024)

Adaptive Automobilfunksysteme - Franchi, Norman; Fischer, Georg; Weigel, Robert (Embedded Software Engineering Kongress, 2013)
Traditionell werden in der Automobilbranche bis dato Systeme mit ausschließlich dedizierten, integrierten Chiplösungen, die jeweils nur auf einen Kommunikationsstandard spezialisiert sind, entwickelt. Im Gegensatz dazu wird in diesem Beitrag ein wegweisendes Integrations- und Prototypingkonzept, aufbauend auf dem Software-Defined-Radio-Prinzip, vorgestellt bei dem eine frei programmierbare Kommunikationsplattform eine Vielzahl unterschiedlicher Funkstandards auf ein und derselben Hardware abbilden kann. Ob diese Funkplattform nun verkehrstelematische Dienste (z.B. eCall-Notruffunktion, Car-2-X-Kommunikation) oder bspw. eine Mobilfunkanbindung (UMTS, LTE) ermöglicht, wird allein durch die Konfiguration der eingebetteten Software und digitalen Schaltkreise festgelegt. Am Beispiel der WLAN-Funkstandards IEEE 802.11b/p sollen anhand eines Demonstrators sowohl die Stärken des Prototypingkonzepts als auch des universellen Funkplattformansatzes für Funksysteme im Fahrzeug verdeutlicht werden.
elib2cris::1512001600,franchi2013c
Keywords: Software Defined Radio; Wireless Vehicular Communication Systems; Car-to-X; IEEE 802.11p

Adaptive Signal- und Kanalemulation mit softwaredefinierter Funktechnik für IEEE-802.11p-basierte Car-2Car-Kommunikation - Franchi, Norman (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2016)

A Deep Neural Network Based Environment Sensing in the Presence of Jammers - Kumar, Atul; Franco De Almeida, Ivo Bizon; Franchi, Norman; Fettweis, Gerhard (2021 IEEE International Conference on Communications Workshops, ICC Workshops 2021 - Proceedings, 2021)
In this paper, we introduce the concept of environment sensing, which is one of the essential requirements for next-generation radio networks to enable highly dynamic radio resource allocation among multiple services. Such requirements motivate the investigation of strategies for transmitter detection, assuming that multiple sensing units (SUs) cooperate to sense the radio environment. A grid-based deployment of the SUs together with randomly placed transmitter units (TUs) and jammer units (JUs) moving with a constant speed of 3 km/h while maintaining the minimum distance between them by 3 m are considered. Active transmitter detection is done using deep neural network. Transmitter detection is performed in two steps, first, jammer detection is performed, and then, legit transmitter detection is performed. Moreover, two well-known performance metrics are employed for verifying the scheme's behavior. The computation of the receiver operating characteristic curve and the probability of detection are used to evaluate the transmitter detection performance. Furthermore, we also consider sensing error performance as a function of the number of SUs. Presented results clearly show that the effectiveness in the detection performance for both JUs and TUs using the proposed deep neural network as compared to conventional cooperative spectrum sensing schemes, such as K-out-of-N, and support vector machine.
Created from Fastlane, Scopus look-up
Keywords: cooperative sensing; Intelligent communications; machine learning; spectrum mobility; spectrum sensing

A Feasibility Study of LTE-V2X Semi-Persistent Scheduling for String Stable CACC - Gonzalez, Arturo; Franchi, Norman; Fettweis, Gerhard (IEEE Wireless Communications and Networking Conference, WCNC, 2019)
A study on feasibility regarding enabling cooperative adaptive cruise control (CACC) through LTE-V2X Semi-Persistent Scheduling (SPS) is considered. A linear time invariant (LTI) CACC model, previously presented in [1] is revisited. The effect of communication delay on the platoon stability, i.e. string stability, in relation to the CACC parameters is then explained. We study the effects on the SPS period limitations imposed by the LTE-V2X standard by modelling it as a communication delay. The performance of CACC under such considerations is presented and further improved by considering multiple SPS parallel sessions. We show that by following simple conditions on the configuration of multiple SPS parallel sessions, the CACC performance can be further improved. Moreover, by considering multiple SPS parallel sessions following these conditions, the SPS period set is refined in granularity. A refined granularity in the SPS period leads to less redundant transmissions from a stability perspective, which effectively translates to a higher efficiency in radio resource usage when compared to single session SPS.
CRIS-Team Scopus Importer:2021-06-08
Keywords: CACC; cooperative platooning; radio resource allocation; semi-persistent scheduling; string stability

A Feature Pyramid Network Based Detection Approach for Multi-Scale Target Detection in Stationary Short-Range Radar - Reitz, Philipp; Veihelmann, Christian Tobias; Künzle, Christian; Franchi, Norman; Weigel, Robert; Lübke, Maximilian (IEEE Wireless and Microwave Technology Conference (WAMICON), 2025)

A Geometry-Based ISAC Channel Model for Vehicle-To-Vehicle Scenarios - Zhang, Guojin; Cai, Xuesong; Franchi, Norman; Lübke, Maximilian (2025 IEEE European Conference on Antennas and Propagation (EuCAP), 2025)
Integrated sensing and communication (ISAC) technique has recently gained significant attention in both academic and industrial sectors, as it can provide both sensing and communication functions using the same transmission and frequency spectrum. In this paper, a geometry-based statistical ISAC channel model for vehicle-to-vehicle (V2V) scenario is established, based on the ray-tracing simulation on the highway scenario at 77 GHz. An improved multipath-component-distance (MCD) threshold-based clustering algorithm is proposed to jointly group the paths for sensing and communication channels as clusters. These clusters are matched to the physical interaction objects in the scenarios. Based on the clustering results, cluster level parameters (i.e., intra-cluster delay, azimuth and Doppler spread) were explored. Furthermore, the clusters contributed from the same physical interaction object in both communication and sensing channels are regarded as ``sharing sensing clusters''. To investigate the correlation and differences between communication and sensing channel, shared degree (SD) metric is analyzed.<br

Analysis of 60 GHz Radar Channel Characteristics in Indoor and Outdoor Environments - Reitz, Philipp; Künzle, Christian; Franchi, Norman; Lübke, Maximilian (Kleinheubacher Tagung, 2024)

A new IP core integration concept for signal manipulation and timing adjustment using a configurable I/O architecture - Franchi, Norman; Weigel, Robert; Cai, Z.; Schmid, J.; Rauch, Hans (23. GI/GMM/ITG Workshop Testmethoden und Zuverlässigkeit von Schaltungen und Systemen, 2011)
Obsolescence of electronic components is a serious problem and challenge for electronics industry affecting nearly every electronic system. The problem of ensuring backward compatibility caused by replacing obsolete system parts must be solved by reproducing the specific functionality and system behaviour of the replaced component. This paper addresses an online configurable I/O architecture that allows user-defined I/O signal manipulations via JTAG interface for FPGA logic designs with integrated IP soft core as replacement for an obsolete chip. In addition to this the flexible configuration affords the opportunity to realize an automated test strategy. Thus embedded-core based system chips can be analyzed, tested and re-/configured automatically.
elib2cris::1512001600,franchi2011a
Keywords: Obsolescence; IP soft core; FPGA; VHDL; JTAG; DFT; pipelining; delay test; signal manipulation; online configuration

A Novel Integrated Power Detection Circuit for Low Noise Amplifiers in Cellular Applications - Spielberger, Alexander; Scheller, Kai; Engelmann, Andre; Franchi, Norman; Weigel, Robert; Pfannenmüller, Christof (IEEE Wireless and Microwave Technology Conference (WAMICON) 2025, 2025)
A novel power sensing method, integrated in low noise amplifier architectures is presented and demonstrated in 130 nm SiGe BiCMOS technology. The power sensor architecture can be utilized to detect blocking signals by supply current varia- tions caused from different amplifier saturation states. Therefore the combined amplifier/power sensor architecture overcomes the need of additional components in the RF signal path for input power sensing. Two sensor architectures are compared while one is implemented. The architectures ability to indicate input power by amplifier saturation is proven by measurement. It is shown that the sensor gives direct feedback at early stages before the amplifier is in full saturation. The amplifier achieves a maximum gain of 14.31 dB and is optimized for the 5G low-band frequency range from 600 MHz to 1 GH
Keywords: Low-noise amplifier; integrated power sensor; mobile communication; Cellular technology; 5G; 4G

A Novel Neuropredictive SAR ADC Architecture for Ultra-Low Power Applications - Spielberger, Alexander; Pfannenmüller, Christof; Spitzkopf, Lucas; Armbrecht, Wolfgang; Schrotz, Albert-Marcel; Weigel, Robert; Franchi, Norman (68th IEEE International Midwest Symposium on Circuits and Systems, 2025)
This paper proposes a new type of neuromophic analog to digital converter, the neuropredictive SAR ADC. By estimation of the next input value using a neuromorphic predictor, the conversion time of a modified SAR ADC and thus the energy consumption of the ADC can be reduced. A demonstrator designed for audio signals shows an energy saving of 41.09% compared to conventional SAR sampling. This ADC architecture is an alternative for ultra-low power application
https://cris.fau.de/converis/publicweb/Publication/342443079
Keywords: neuromorphic adc; neuropredictive SAR; SAR; ultra-low power

Antenna Setup for Future Joint Radar-Communications – Characteristics and Mounting Positions - Lübke, Maximilian; Fuchs, Jonas; Dubey, Anand; Frank, Martin; Franchi, Norman; Lurz, Fabian (Advances in Radio Science : Kleinheubacher Berichte, 2023)

Applying reliability theory for future wireless communication networks - Hößler, Tom; Scheuvens, Lucas; Franchi, Norman; Simsek, Meryem; Fettweis, Gerhard P. (IEEE International Symposium on Personal, Indoor and Mobile Radio Communications, PIMRC, 2018)
Enhancing the connectivity reliability is one of the most challenging requirements for the design of future wireless communications systems. The scope of this paper is to leverage the existing tool set of reliability theory for enabling reliable communication in wireless systems. Definitions, concepts, and methods of reliability theory are applied and extended to wireless communications networks, which are modeled as a repairable system. The steady-state and transient system behaviour are considered. Two new key performance indicators (KPIs) for the reliability analysis of wireless communications systems are introduced, namely mean time to first failure (MTTFF) and interval reliability (IR), and a closed form expression is derived for the MTTFF. By evaluating an exemplary scenario, the trade-off between availability, reliability and throughput is discussed.
CRIS-Team Scopus Importer:2021-06-08
Keywords: 5G; Availability; Interval reliability; Mean time to first failure; Reliability theory; URLLC

A secure and resilient 6G architecture vision of the German flagship project 6G-ANNA - Hoffmann, Marco; Kunzmann, Gerald; Dudda, Torsten; Irmer, Ralf; Jukan, Admela; Macher, Gordana; Ahmad, Abdullah; Beenen, Florian R.; Broring, Arne; Fellhauer, Felix; Fettweis, Gerhard; Fitzek, Frank H.P.; et al. (IEEE Access, 2023)
The 6th generation of wireless mobile networks is emerging as a paradigm shifting successor to unifying the experience across the physical, digital, and human worlds, pushing boundaries on performance in capacity, throughput, latency, scalability, flexibility, and reliability, while prominently addressing new major factors, including sustainability, security and privacy, as well as digital inclusion. Many research institutions and initiatives worldwide have started investigations to make 6G a reality by approximately 2030. In Germany, federal funding from the German Ministry of Education and Research (BMBF) supports a large-scale 6G initiative, with its lighthouse project, called 6G-ANNA. The core aim of this project is to develop the key aspects of a holistic, sustainable, secure, and resilient 6G system design that will simplify and improve the interaction between humans, digital assets, and the physical environment. This paper shares the vision of the project’s main technical working areas and advances, spanning topics from radio access, integration of multiple networks, as well as automation and simplification in networking to new applications and testbed scenarios, including real-time digital twins and extended reality. The industrial impact and relevance of standardization makes 6G-ANNA uniquely positioned to lead and realize the vision of next-generation wireless mobile network technologies, systems, and applications.<br
Keywords: 6G; communications systems; wireless communications; network architecture; resiliency; security

Aspects on Applying and Operating Campus Networks in Agriculture - Hecker, Andreas; Striller, Benjamin; Boye, Fredrik; Franchi, Norman; Freytag, Hagen (VDI Verlag GMBH, 2022)
Private (campus) networks with a cloud-based architecture provide a solution for automated data communication in agriculture and effective management of farm businesses, making it possible to achieve increasing economic and ecological targets. The experimental test field LANDNETZ builds and tests mobile private networks, which, for the first time, have been designed for agricultural applications and farm environments [1]. The goal of LANDNETZ is to develop networking solutions that operate on the basis of use cases (application-specific operation) and to investigate operational aspects of private campus networks and their potential for improvements. In this paper, the authors introduce recent examples of agricultural applications, outline their requirements for a campus network solution, and present necessary aspects of operating a campus network.
CRIS-Team Scopus Importer:2024-12-16

A Study on Link Adaptation Techniques for IEEE 802.11bd Based eV2X Communications - Anwar, Wagar; Franchi, Norman; Fettweis, Gerhard (IEEE Vehicular Technology Conference, 2021)
The ultra-high reliability is an essential requirement for enhanced vehicle-to-everything (eV2X) use cases. In order to ensure the desired reliability in a time-varying channel, link adaptation is required. Therefore, the current and upcoming technologies use adaptive modulation and coding (AMC) schemes. By using AM C, the reliability and data rates could be adapted according to the channel conditions. To further improve reliability, concepts like multi-connectivity could also be used. In multi-connectivity, redundant data can be transmitted using multiple simultaneous links and combined at the receiver to improve reliability. However, this requires link adaption in terms of both numbers of multiple links and AMC. In this paper, we evaluate different link adaptation schemes for IEEE 802.11bd based on single-link and multi-connectivity communications. For single-link communications, we generate channel quality indicators (CQI) based on various signal-to-interference-plus-noise ratio (SINR) mapping techniques, e.g., exponential effective SINR mapping (EESM), received bit information rate (RBIR), and recently proposed enhanced EESM (eEESM). The performance of these schemes is evaluated in terms of achieved reliability and data rates. Results show that eEESM achieves close to optimal performance. In the case of multi-connectivity, different MCS and link adaptation schemes are evaluated. It is shown that joint adaptation of MCS and the number of links deliver better performance in terms of data rates and link utilization.
Created from Fastlane, Scopus look-up
Keywords: 5G and beyond; Adaptive Modulation and Coding; IEEE 802.11bd; Link adaptation; Multi-connectivity

Automotive meets Adaptive Wireless Communication - Franchi, Norman; Spiteller, Florian; Weigel, Robert (4. GMM-Fachtagung Automotive meets Electronics (AmE), 2013)
Die Einbindung drahtloser Technologien in Fahrzeuge wird in den kommenden Jahren zunehmend an Bedeutung gewinnen. Die Vernetzung des Automobils mit mobilen Endgeräten der Passagiere sowie mit anderen Fahrzeugen und der Umwelt wird dabei als neue Schlüsselkompetenz für zukünftige Fahrzeugtechnik gesehen. In der Automotive-Branche werden bisher meist dedizierte Systeme mit integrierten Chiplösungen eingesetzt, deren Funktionen kaum dynamisch angepasst werden können. In diesem Beitrag wird daher ein modulares Konzept vorgestellt, das auf dem Software-Defined-Radio-Prinzip aufsetzt und großes Potential für die Entwicklung adaptiver und kosteneffizienter Umsetzungsformen von sog. Wireless Vehicular Communication Systems bietet. Mit Hilfe der exemplarischen Umsetzung eines neuartigen Prototyping-Ansatzes werden – am Beispiel der beiden automotive-relevanten Funkstandards IEEE 802.11bTM und IEEE 802.11pTM – sowohl die Stärken des Ansatzes selbst als auch der SDR-basierten Realisierungsform von flexiblen Funksystemen verdeutlicht.
elib2cris::1512001600,franchi2013
Keywords: Software Defined Radio; Wireless Vehicular Communication Systems; Rapid-SDR-Prototyping; IEEE 802.11p; IEEE 802.11b; USRP

Cognitive Multi-Radio as Enabler for Deterministic Dynamic Spectrum Access - Kloc, Matej; Franchi, Norman; Gardill, Markus; Weigel, Robert (Wireless Innovation Forum European Conference on Communication Technologies and Software Defined Radio (WInnComm-Europe), 2015)
Cognitive radio (CR) is a promising approach to enable dynamic spectrum access (DSA) and to handle spectral efficiency in licensed frequency bands. In this presentation, two new concepts, called cognitive multi-radio (CMR) and deterministic dynamic spectrum access (D-DSA), are introduced. These concepts help to increase the spectrum agility and hence to improve the deterministic broadband spectrum access in unlicensed industrial, medical and scientific (ISM) bands, where shared spectrum lead to interferences and/or collisions, which consequently degrade transmission performance. Here, the CMR-based D-DSA approach is discussed in context with industrial wireless communications (IWC), where a real-time capable transmission behavior with high determinism, high reliability and low-latency (round-trip latency budget ≤ 1 ms) is required. In addition, a CMR hardware architecture, which is based on the software-defined radio (SDR) principle, is proposed.
elib2cris::1512001600,kloc2015

Communication Abstraction Supports Network Resource Virtualisation in Automation - Olaya, Santiago Soler Perez; Wollschlaeger, Martin; Krummacker, Dennis; Fischer, Christoph; Schotten, Hans D.; Guillaume, Rene; Walewski, Joachim W.; Franchi, Norman (IEEE International Symposium on Industrial Electronics, 2018)
In this contribution, an abstraction model for communication in distributed automation applications is proposed. This model facilitates a stringent delineation of the application and communication network, and fosters topics such as the introduction of service-oriented communication functions into automation and the abstraction of heterogeneous communication networks. This is necessary to support the flexibility demands of future industrial applications, realizable with modern communication concepts like Software Defined Networks. The paper proposes a classification of communication requirements, and discusses implementation aspects.
CRIS-Team Scopus Importer:2021-06-08
Keywords: Abstraction Model; Industrial Communication; Industrial Network Management; Network Slice

Control Loop Aware LTE-V2X Semi-Persistent Scheduling for String Stable CACC - Gonzalez, Arturo; Franchi, Norman; Fettweis, Gerhard (IEEE International Symposium on Personal, Indoor and Mobile Radio Communications, PIMRC, 2019)
An analytical method for computing the channel access delay budget between consecutive kinematic updates among a vehicle pair in a cooperative adaptive cruise control (CACC) enabled platoon under string stability conditions is presented. It is shown that even first-order approximations of the complex exponential delay term yield good numerical results. The method also indicates when communication in CACC is not required. The calculated channel access delay budget is used to obtain the semipersistent scheduling period for string stable CACC under LTE-V2X Mode 3 communication. Furthermore, an efficient semi-persistent scheduling algorithm capable of allocating heterogeneous periods and supporting multiple platoons is presented and validated with two examples.
CRIS-Team Scopus Importer:2021-06-08
Keywords: CACC; LTE-V2X; platooning; radio resource allocation; semipersistent scheduling; string stability

ConTST: Predicting Mobile Subnetwork Encounters in Dynamic Factories with Time Series Transformers - Müller, Kilian; Franchi, Norman (2024 IEEE 100th Vehicular Technology Conference, 2024)
Subnetworks with different levels of autonomy are an integral part of 6G, helping to improve local connectivity, resilience, and security. These are especially interesting for cooperative robotics on shop floors, where multiple robots can come together and directly exchange task-specific data in near real-time without stressing the parent network. The same sub-network capabilities are currently implemented into Automated Guided Vehicles (AGVs), allowing non-time-critical data from near monitoring equipment to be offloaded via AGVs instead of streaming them directly to the shop floor's parent network, relieving the parent network in the process. However, to do so, an efficient approach is needed, which (1) can predict future encounters between AGVs and monitoring nodes on a node-to-node basis with minimal traffic overhead, (2) does not require heavy computation like machine learning on highly constraint nodes, and (3) does not need access to AGVs' subnetwork controllers and routing tables.Introducing ConTST (CONnection forecasting with Time Series Transformers), a semi-passive, probabilistic approach for predicting future data offloading possibilities to autonomous mobile subnetworks on a node-to-node basis from only successfully received bundles in the network edge. We utilize a single, small probabilistic time series transformer model in the network edge, minimal additional metadata per bundle, and some tracing bundles to successfully estimate future encounters from past encounters. Nodes optimize their offloading strategy greedily by only utilizing precomputed encounter tables from the edge services, making this approach compatible even with the most constrained IoT devices. We extensively evaluate our approach on our shop floor simulator and show that it is resilient against outliers, capable of predicting future encounters, and can reliably optimize overall offloading Quality of Service (QoS) metrics like bundle latency or lost bundle ratio.<br

Coordinated Multipoint JCAS in 6G Mobile Networks - Su, Yanpeng; Lübke, Maximilian; Franchi, Norman (IEEE Access, 2024)
Joint communications and sensing (JCAS) is regarded as a key technology of 6G communications since it allows the integration of sensing functions into communications networks with lower hardware costs, less energy consumption, and saved spectrum. As distributed sensing benefits from increased spatial diversity and accuracy, the combination of coordinated multipoint (CoMP) transmission technology and JCAS has become an attractive research direction. CoMP transmission has been applied in 4G and 5G communications networks due to its attractive capability in suppressing inter-cell interference and improving channel capacity, while CoMP sensing and CoMP JCAS have been widely discussed in recent years. However, relevant researches mainly focus on waveform design and optimization issues in the processes of CoMP signal transception and processing, while their system architecture and operation modes are less discussed. To fill the blank in these areas and discuss the benefits provided by CoMP JCAS, in this work, based on the modern CoMP transmission technologies in state-of-the-art mobile network architecture, we analyze the network architecture and required enabler technologies of CoMP JCAS in future mobile networks, focusing on the sensing aspect. In addition, we propose the potential sensing operation and clustering types and discuss their respective advantages and shortcomings. In the simulation, the sensing coverage and accuracy of different CoMP sensing types and conventional standalone sensing are compared. The simulation results show that CoMP sensing outperforms conventional single-radar sensing in accuracy, and the difference between them increases with the distance between the sensors. In addition, it is described that the coordinated passive sensing scheme extends the service area, while the active sensing scheme benefits from higher accuracy with the same bandwidth.<br
Keywords: 6G; B5G; coordinated multipoint (CoMP); cloud radio access network (C-RAN); joint communications and sensing (JCAS); mobile network; networked radar.

D2D sub-THz Industrial Radio System for 6G Use Case Definition RF Transceiver Requirements Analysis and Feasibility Considerations - Fink, Lucas; Seifaei, Masoud; Benzin, Andreas; Osterland, Dennis; Franchi, Norman (European Wireless 2024, 2024)
In industrial environments, it is necessary to transfer data between sensors, actuators, and control units with high data rates and low latency. The development of the sixth generation (6G) of mobile communications enables new frequency bands like D-band (110–170 GHz) for wireless transmission in the sub-terahertz (sub-THz) range. In this frequency range, ultra-broadband transmission enables high throughput between robots and machines in production plants using a wireless link. This work introduces a high-throughput short-range point-to-point use case for sub-THz communications systems in an industrial environment to enhance or replace wired industrial fieldbus and Industrial Ethernet networks. The aim is to make industrial communications networks more flexible, using the high transmission capacity to increase data rates and decrease latency by implementing D2D communications. After defining the use case, requirements for the hardware components of a sub-THz transceiver including a phased array antenna are investigated. The path loss is calculated depending on predefined link distance, SNR at the receiver, achievable data rate, and minimum signal integrity at the ADC are determined using state-of-the-art transceiver system specifications. With the results, a statement about the principle feasibility of the use case is made based on the specifications of a state-of-the-art sub-THz radio system.<br
Keywords: 6G; digital twin; industry 4.0; Industrial Ethernet; sub-terahertz; wireless communications

Data Consistency Determination with Multi-Event Detection for Heterogeneous Sensors - Ruhland, Tim; Lübke, Maximilian; Tobola, Andreas; Franchi, Norman (IEEE I2MTC – International Instrumentation and Measurement Technology Conference, 2025)

Data Quality in IoT Temperature Sensor Systems: Demonstrated on Time-Dependent Temperature Fluctuations - Ruhland, Tim; Tobola, Andreas; Scholl, Christoph; Lübke, Maximilian; Franchi, Norman (IEEE Sensors Journal, 2024)
The growing integration of the Internet of Things (IoT) in Industry 4.0 is primarily attributed to its low cost and high adaptability. Our research addresses the expansive application of IoT temperature sensor systems within industrial environments characterized by harsh conditions and rapid temperature fluctuations. Typically, these sensors lack awareness of the data quality they measure and provide. The article mitigates this limitation by introducing data quality models that enhance the accuracy and timeliness of temperature sensor data. These models interpret temperature readings affected by thermal lag and delayed response times. Timeliness is determined using three distinct methods that reflect data volatility, while accuracy is assessed by applying the Savitzky-Golay filter, which provides temperature transients. Both data quality models precede a knowledge-based approach, accumulating necessary information for the sensor system through calibration. These quality categories are combined into a unified Quality of Sensing (QoS) parameter, utilizing fuzzy logic to abstract the quality dimensions, thereby having profound implications for the IoT sensor system. This methodology has been encapsulated within a comprehensive framework and validated using an industrial-grade IoT temperature sensor in a real-world measurement setup. By transcending the conventional reliance on raw sensor outputs, our framework empowers the extraction of intrinsic quality information associated with each temperature reading, enhancing the resilience and reliability of IoT temperature sensor systems.<br

Deriving an Empirical Channel Model for Wireless Industrial Indoor Communications - Trasl, Andreas; Hosler, Tom; Scheuvens, Lucas; Franchi, Norman; Fettweis, Gerhard P. (IEEE International Symposium on Personal, Indoor and Mobile Radio Communications, PIMRC, 2019)
Wireless system design on the physical layer is usually evaluated using comprehensive channel models. However, there is still a lack of publicly available stochastic channel models tailored to industrial use cases, which are recently considered more frequently. This paper presents the derivation of such a channel model for the 5 GHz ISM band and its parametrization. The frequency-selective behaviour is modeled by the Saleh-Valenzuela model. Based on a measurement campaign, the parameters of this model for a factory environment are determined and published the first time for the 5 GHz ISM band. Spatial correlation is modeled by the Kronecker model. The temporal variation of the channel is based on a theoretically derived Doppler spectrum assuming Laplacian distributed angle of arrivals. In addition to the description of the model components, key issues and common mistakes while constructing a channel model for industrial applications are discussed in order to advance the design and the deployment of future wireless industrial communications systems. The derived channel model is used in IEEE 802.11ax link layer simulations. It is shown that for industrial use cases specially tailored channel models are needed.
CRIS-Team Scopus Importer:2021-06-08
Keywords: channel model; industrial environment; power delay profile; Saleh-Valenzuela model; WLAN

Design von adaptiven Automobil-Funksystemen mittels Rapid-SDR-Prototyping - Franchi, Norman; Fischer, Georg; Weigel, Robert (RADCOM 2013, 2013)
In den kommenden Jahren wird die Einbindung drahtloser Technologien in unsere Fahrzeuge zunehmend an Bedeutung gewinnen. Dabei wird die informationstechni- sche Vernetzung des Automobils mit anderen Fahrzeugen, mit seiner Umgebung so- wie mit mobilen Endgeräten der Passagiere als neue Schlüsselkompetenz für zukünfti- ge Fahrzeugtechnik gesehen. Bisher werden in der Automobilindustrie zur Abbildung unterschiedlicher Kommunikationsstandards meist jeweils dedizierte Chiplösungen eingesetzt, deren Funktionen kaum dynamisch angepasst werden können. In diesem Beitrag wird daher ein modulares, Software-basiertes Prototyping-Konzept vorgestellt, mit dessen Hilfe der Entwurf und die Entwicklung von flexiblen Wireless Vehicular Com- munication Systems ermöglicht werden kann. Am Beispiel der automotive-relevanten Funkstandards IEEE 802.11b und IEEE 802.11p sollen anhand einer Prototypenumset- zung sowohl die Stärken des Prototyping-Konzeptes als auch einer SDR-basierten Rea- lisierungsform von Funksystemen im Fahrzeug verdeutlicht werden.
elib2cris::1512001600,franchi2013a

Dual-Task Supervised Learning for Distributed Spectrum Monitoring Applications - Shatov, Victor; Shanin, Nikita; Veihelmann, Christian Tobias; Perner, Bastian; Franchi, Norman; Lübke, Maximilian (EuCNC & 6G Summit, 2025)

Enabling Mobility-Oriented JCAS in 6G Networks: An Architecture Proposal - Rosemann, Philipp; Partani, Sanket; Miranda, Marc; Mähn, Jannik; Karrenbauer, Michael; Meli, William; Hernangómez, Rodrigo; Lübke, Maximilian; Kochems, Jacob; Köpsell, Stefan; Aziz-Koch, Anosch; Askar, Ramez; et al. (2024 IEEE 4th International Symposium on Joint Communications & Sensing (JC&S), 2024)

Energy Savings in 5G-Advanced Radio Access Networks: Downlink Signaling Adaptation - Vatanian, Nazanin; Oliveira da Costa, Gustavo Wagner; Roth-Mandutz, Elke; George, Geordie; Franchi, Norman (2024 IEEE 100th Vehicular Technology Conference (VTC2024-Fall), 2024)
As energy consumption of cellular networks continues to rise, its impact on the environment and operating costs have become a pressing concern. With the goal of improving energy efficiency by reducing the energy consumption, Network Energy Savings (NES) is considered by 3GPP as one of the key enhancements of the 5G-Advanced and 6G standardization. This paper addresses a key time-domain NES technique being standardized by 3GPP, namely, adaptation of downlink common signals, providing a comprehensive evaluation based on system level simulations. We propose a novel approach to dynamically adapt the periodicity of downlink common signals based on network demand. The results demonstrate great benefits of the dynamic adaptation of downlink common signals in terms of energy saving gain
Keywords: network energy savings; NES; energy efficiency; power saving; 5G NR; common signals adaptation; 5G-Advanced; 6G

Evaluating Communication and Sensing Quality in Phase-Modulated FMCW Radar - Bönsch, Jonas; Reitz, Philipp; Franchi, Norman; Lübke, Maximilian (5th IEEE International Symposium on Joint Communications & Sensing, 2025)

Evaluating RF Hardware Characteristics for Automotive JCRS Systems Based on PMCW-CDMA at 77 GHz - Lübke, Maximilian; Su, Yanpeng; Franchi, Norman (IEEE Access, 2023)

Evaluating Synthetic Data Potential for 60 GHz FMCW Radar Simulations with Real Measurements - Reitz, Philipp; Maiwald, Timo; Franchi, Norman; Weigel, Robert; Lübke, Maximilian (11th Microwave and Radar Week, 2024)
A fully integrated simulation environment for an FMCW radar system in an indoor environment operating at 60 GHz has been proposed. The simulation of the entire signal processing chain, starting with a CST simulation of the antenna pattern and extending to the radar signal processing, enabled the demonstration of the radar hardware’s and the channel’s inherent properties. Measurements and simulations have revealed the inherent fluctuation paths of a human target by showing a variation of 10 dB in the reflection power of the human and 0.5 m in the range profile in measurements. The papers results could demonstrate that synthetic datasets can be considered valid alternatives in radar detection. The channel properties could be examined by investigating different up-tilt configurations, and problems such as ground reflections caused by side lobes and multipath propagation within the human target could be further investigated.<br
Keywords: radar cross section; FMCW radar; simulation and measurement; mm-wave

Evaluating the Performance of UE-Side Sensing in Multistatic ISAC Systems for Highway Scenarios - Gröneweg, Jan-Steffen; Gherekhloo, Soheil; Lübke, Maximilian; Franchi, Norman (IEEE International Symposium on Joint Communications & Sensing, 2025)

Evaluation of the Interference Performance of FMCW Radar Sensors in Dense Indoor Environments - Reitz, Philipp; Künzle, Christian; Franchi, Norman; Lübke, Maximilian (IEEE Access, 2024)
Frequency-modulated continuous-wave (FMCW) radars are becoming increasingly important in industrial applications due to their low cost, simple signal processing, and high resolution. The research is driven by the growing trend of radar applications in industrial settings, including tasks like autonomous robot navigation, radar-based monitoring of humans, and enhancing safety across various scenarios, such as smart factories, traffic control, or environmental monitoring. The network of distributed sensor nodes is a feature to be implemented by the sixth generation of wireless mobile networks. As a result, 6G will become an enabler technology that will develop even further use cases and advance the expansion of these technologies. Therefore, the mutual interference of these sensor systems is becoming highly relevant since they can be avoided by scheduling the individual resources of the sensor nodes by a network structure. This paper investigates the interference behavior of FMCW radar sensors in a dense indoor scenario. In these environments, in particular, the reliability of the sensor system plays an important role, and disruption can have critical consequences like not recognizing a target, triggering a false alarm, or the complete failure of the sensing. To correctly classify the expected interference in the overall context, the paper investigates the physical layer effects on the performance, such as multipath propagation, channel spread, delay, Doppler shift, and attenuation. By evaluating these effects using state-of-the-art signal processing, it was revealed that a high channel spread in particular and the dynamics of the radar channel can significantly reduce the detection quality, as the interference power can exceed the received power by up to 20 dB, depending on the scenario. The simulation results given in this paper show that a potential communication between the radars and compliance with a synchronization delay, the interference problems can be reliably prevented with an appropriately designed anti-aliasing filter. Our simulations have quantified the detection performance under interference through the entire signal chain by evaluating the physical layer, the radar signal processing with non-idealities, and the hardware. The paper has investigated interference probability in indoor environments by examining radars with uncoordinated transmissions. Integrating findings from the physical propagation characteristics, the deviations in chirp durations, and the frequency of interference cases offers insights into the potential risk of interferenc
Keywords: Interference; Chirp; Radar; Sensors; Delays; Radar signal processing; Time-frequency analysis; Frequency modulation; Continuous wavelet transforms; Channel estimation; Robot sensing systems; Radar signal processing; Sensor systems; Physical layer; Wireless sensor networks; Wireless communication; Environmental monitoring; Telecommunication traffic; Detection algorithms; Performance evaluation; Channel simulation; CIR; FMCW radar; industrial radar; interference; interference mitigation; mmWave; multipath

Feedforward Filter Design for CACC with N - Vehicle Look Ahead: A Frequency Domain Approach for Further Optimization of Radio Resource Usage - Villamil, Andres; Gonzalez, Arturo; Franchi, Norman; Fettweis, Gerhard (IEEE Vehicular Technology Conference, 2020)
In [1] the upper-bound on the communications interval required to achieve string stability for a Cooperative Autonomous Cruise Control (CACC) system, i.e. the Maximum Allowable Transmission Interval (MATI), was found for the one-vehicle look ahead topology (vehicles communicating only with their immediate predecessors). Obtaining the MATI permitted to exploit the CACC dynamics as degrees of freedom for radio resource allocation while guaranteeing the proper functioning of CACC [2]. By transmitting only at the necessary update rate dictated by the system dynamics, the demands on the communication network are relaxed compared to an agnostic static allocation. This paper considers additional information from N preceding vehicles for further relaxation of the communications requirements. The hypothesis is that by over-hearing transmissions of additional predecessors, the update rate between vehicles can be reduced while maintaining string stability. Since overhearing state information of additional previous predecessors requires to process their information coherently, the design of N feedforward filters is necessary when considering N previous vehicles. In this work, we propose a methodology to design the feedforward filters that optimizes the MATI within the platoon based on a frequency domain analysis by posing an optimization problem. We show that transmission intervals on the wireless links can be relaxed up to 8x when a two-vehicle look ahead (2VLA) network topology is considered and up to 9x for a three-vehicle look ahead (3VLA) topology.
CRIS-Team Scopus Importer:2021-06-08
Keywords: CACC; Maximum Allowable Transmission Interval; Networked Control Systems; Platooning; String Stability

FLINT: Performance-Aware In-Network Computing for Dynamic 6G Sub-Networks - Müller, Kilian; Zhang, Jiajing; Vossiek, Paul; Shafaei, Sina; Fitzek, Frank H.P.; Franchi, Norman (IEEE International Conference on Communications (ICC), 2025)

Framework for Adaptive Controller Design Over Wireless Delay-Prone Communication Channels - Scheuvens, Lucas; Simsek, Meryem; Noll-Barreto, Andre; Franchi, Norman; Fettweis, Gerhard P. (IEEE Access, 2019)
Control over wireless channels promises to be a great enabler for an interconnected world. Historically, the 'control engineering' and 'wireless communications' domains were seen as separate, but with upcoming 5G networks, joint design of wireless control systems promises large gains in both the domains for a wide range of applications. By means of a typical industrial use case of the automated guided vehicles (AGVs), we present a methodology to analyze the latency requirements along with the wireless links from a controller to a plant (downlink) and from a plant to its controller (uplink). From the perspective of a Wireless Communications Engineer, we present a framework to analyze the basic properties of the resulting control cycle in order to derive feasible latency values that differ from the commonly found values in the communications literature. Also, we highlight an approach to derive the proportional-derivative (PD) controller parameters that yield the best control performance according to the integral of absolute error (IAE) criterion. At last, we present the idea of a cross-domain manager (CDM) that is able to translate (in real-time) the current network performance metrics to optimal controller gains.
CRIS-Team Scopus Importer:2021-06-08
Keywords: 5G; control over wireless; networked control systems; tactile Internet; URLLC; wireless factory automation

Full Physical Layer Simulation Tool to Design Future 77 GHz JCRS-Applications - Lübke, Maximilian; Su, Yanpeng; Cherian, Athira Jess; Fuchs, Jonas; Dubey, Anand; Weigel, Robert; Franchi, Norman (IEEE Access, 2022)
Vehicular communication systems get more and more attention with the upcoming fifth and sixth generation. Hereby, the focus lies on the development of the co-design or co-existence of communications and sensing. So called joints communications and radar sensing systems are seen as one key technology of 6G. As joint systems will have shared waveforms and hardware platforms, there is a huge benefit in cost and space which is one essential argument for the automotive industry. However, to design such a system for new applications like platooning or intersection assistance a physical layer has to be set up to represent the real physical layer properly. The proposed system design closes the lack of such a simulation tool and allows for full physical layer simulations, including e. g. the hardware non-idealities and the channel model for 77 GHz. The whole signal processing chain of the physical layer is built up and will be integrated in the higher layer state-of-the-art simulation frameworks like Veins or Artery in the next step. The communications design is developed in Simulink, whereas the sensing part is discussed. The proposed communications architecture covers several transmission approaches (serial, parallel), a CDMA based spreading, a radio frequency representation, the channel (simulated in a 3D-Ray-Tracing-tool) and the receiver structure (e. g. the synchronisation or the channel estimation). Several design criteria are discussed, like the serial or parallel design architecture, the maximum ratio combining or the phase and frequency compensation method. The whole system architecture is freely available (https://doi.org/10.5281/zenodo.6482565) and in consequence, the different signal blocks and parameters can be enabled or disabled for evaluations according to future design criteria requirements. <br

German Perspective on 6G – Use Cases, Technical Building Blocks and Requirements Insights by the 6G Platform Germany - Franchi, Norman; Dressler, Falko; Ergenc, Doganalp; Guter, Paulus; Lassen, Vincent; Lübke, Maximilian; Veihelmann, Christian Tobias; Baradie, Shaden; Bassbouss, Louay; Bathelt, Andreas; Eichhorn, Fabian; Fink, Lucas; et al. (FAU University Press, 2024)

How Connected Cars Can Improve Solar Forecasting - Expanding the Scale of Local Sensor Networks - Veihelmann, Christian Tobias; Lübke, Maximilian; Franchi, Norman (41st European Photovoltaic Solar Energy Conference and Exhibition, 2024)

How Connected Cars Could Capture Cloud Dynamics for Solar Forecasting—Evidence from Two Simulation Scenarios - Veihelmann, Christian Tobias; Reitz, Philipp; Lübke, Maximilian; Franchi, Norman (Solar RRL, 2024)

Hybrid Beamforming Design with Physical Layer Simulation Tool for JCAS Applications - Zhang, Mengyu; Reißland, Torsten; Franchi, Norman; Fischer, Georg; Weigel, Robert (2024 Asia-Pacific Microwave Conference, 2025)
This paper presents a Simulink-based physical layer simulation tool that integrates non-ideal hardware components for simulating OFDM-based Joint Communications and Radar Sensing systems. The tool aims to implement hybrid beamforming (HBF) designs in a more realistic environment. In addition, an enhanced HBF algorithm has been formulated, enabling multi-user (MU) communication and sensing while mitigating inter-user interference. Simulation results using the proposed tool show that non-ideal Hardware (HW) defects limit the system's performance, but hybrid beamforming significantly improves it.<br
Keywords: Hybrid Beamforming; Joint communications and radar sensing (JCAS); OFDM; Physical layer simulation tool; Simulink

Hybrid Predictive Modeling for Single-Sensor Data Consistency in Industrial IoT - Ruhland, Tim; Müller, Kilian; Lübke, Maximilian; Tobola, Andreas; Franchi, Norman (21st International Conference on Distributed Computing in Smart Systems and the Internet of Things, 2025)

Hybrid V2X Communications: Multi-RAT as Enabler for Connected Autonomous Driving - Jacob, Richard; Franchi, Norman; Fettweis, Gerhard (IEEE International Symposium on Personal, Indoor and Mobile Radio Communications, PIMRC, 2018)
Exploiting the full potential of automated driving systems requires reliable wireless communication enabling network connectivity and cooperation among vehicles. Multiple V2X technologies are addressing the requirements of connected autonomous driving applications. Recent investigations have shown that none of the technologies is flexible and reliable enough to serve the diverse requirements in terms of delay, reliability and throughput under the various circumstances observed by vehicles. Hybrid V2X communications enables the coordination of multiple communication technologies to efficiently adapt to the time-varying channel and road traffic conditions. Further it allows to increase reliability and throughput of transmissions by combining multiple RATs in parallel. This work gives an overview of the potential, challenges and main design aspects of hybrid V2X communications considering the latest technological developments.
CRIS-Team Scopus Importer:2021-06-08
Keywords: Connected autonomous driving; Diversity; Hybrid communications; Multi-RAT; Profile selection; V2X

IC-in-the-Loop - Ein innovatives Verfahren zur automatisierten Analyse, Verifikation und Re-/Konfiguration von Embedded-Core basierten Chipsystemen - Franchi, Norman; Heinz, Christian (Elektrotechnik, 2010)
Der Veruegbarkeitszeitraum von elektronischen Bauteilen wird immer kuerzer. Obsoleszenz ist ein Problem, fuer das es verschiedene Loesungsansaetze gibt. Die radikalste und teuerste Loesung ist ein komplettes Redesign der gesamten Systembaugruppe rund um eine neue Komponente. Eine angemessene Alternative hierzu ist beispielsweise der Austausch der nicht mehr veruegbaren Hardware mit einer System-on-a-Chip (SoC)-Variante, welche mit eingebetteten Core-Logikbausteinen (Black-Boxes) die jeweils obsolete Schaltungseinheit emuliert. Bei dieser Vorgehensweise werden digitale, analoge und Mixed-Signal-Funktionseinheiten von veralteten bzw. abgekündigten Bauelementen in Form von IP Cores (Hard- sowie Soft-Cores) auf integrierten Schaltkreisen (ICs), wie ASICs oder FPGAs, neuer Chipgenerationen integriert und danach auf redesignten Elektronikbaugruppen verbaut.
elib2cris::1512001600,franchi2010
Keywords: Obsoleszenz; Embedded Cores; SoC; FPGA; VHDL; Redesign

Impact of parallel interference on FMCW radar detection in indoor environments - Reitz, Philipp; Franchi, Norman; Lübke, Maximilian (13th edition of the IEEE-APS Topical Conference on Antennas and Propagation in Wireless Communications, 2024)

Improving Resource Efficiency of PMCW-Based JCRS Systems: Simultaneous Transmission of Pilot and Data via Orthogonal Codes - Su, Yanpeng; Shatov, Victor; Lübke, Maximilian; Franchi, Norman (IEEE International Symposium on Personal, Indoor and Mobile Radio Communications - Workshop: International Workshop for Integrated Sensing and Communication, 2023)

Joint Radar and Communications: Architectures, Use Cases, Aspects of Radio Access, Signal Processing, and Hardware - Shatov, Victor; Nuß, Benjamin; Schieler, Steffen; Bishoyi, Pradyumna; Wimmer, Lara; Lübke, Maximilian; Keshtiarast, Navid; Fischer, Christoph; Lindenschmitt, Daniel; Geiger, Benedikt; Thomae, Reiner S.; Fellan, Amina; et al. (IEEE Access, 2024)
Keywords: 6G; joint communications and sensing (JCAS); joint radar and communications (JRC); integrated sensing and communications (ISAC); radar-communications (RadCom); radio access network (RAN) architecture

Joint synchronization in macro-diversity multi-connectivity networks - Schwarzenberg, Nick; Burmeister, Friedrich; Wolf, Albrecht; Franchi, Norman; Fettweis, Gerhard (IEEE Vehicular Technology Conference, 2019)
Multi-connectivity is a key enabler for realtime applications demanding high reliability such as connected vehicles. Employing macro-diversity with distributed transceivers has the advantage of mitigating large-scale losses such as shadowing, but may incur time offsets between packets, requiring the receiver to synchronize to each packet individually. Since packet detection is prerequisite for any downstream receiver processing, synchronization can become a bottleneck to achieving high reliability. In this paper, we propose a concept to improve receiver performance in macro-diversity multi-connectivity networks in case of time offsets between packets, for instance, due to loose synchronization of distributed transmitters. By buffering the inputs of parallel receiver paths and allowing for iterative synchronization, successfully detected packets can serve as extended correlation sequence to detect previously undetected packets which thereby become available to diversity combining. Taking link-level simulations of IEEE 802.11 (WLAN) as an example, we demonstrate the efficacy of such Joint Synchronization (JS) and provide first numerical results. We see an SNR gain of about 1 dB in the mid-SNR range, which is equivalent to a packet error rate reduction by an order of magnitude for four-fold diversity. With power consumption in mind, we consider the trade-off between implementation complexity and the gain of JS. We conclude that JS is a viable backwards-compatible approach to improve diversity combining of delayed packets in multi-connectivity networks.
CRIS-Team Scopus Importer:2021-06-08
Keywords: Distributed Transceivers; Diversity; Iterative Synchronization; Multi-Connectivity; Packet Detection; URLLC

Leveraging gradient-boosted trees to combine FFT, correlation and Fréchet-distance features for clear-sky detection - Veihelmann, Christian Tobias; Seifaei, Masoud; Lübke, Maximilian; Franchi, Norman (40th European Photovoltaic Solar Energy Conference and Exhibition, 2023)

Low Latency Evaluation of an Adaptive Industrial Wireless Communications System for ISM Bands - Kloc, Matej; Franchi, Norman; Gardill, Markus; Weigel, Robert (IEEE Topical Conference on Wireless Sensors and Sensor Networks (WiSNet), 2016)
Low latency and highest transmission reliability are the key challenges for enabling time-critical industrial wireless applications, e.g. in factory automation. Both are significantly determined by the rough and dynamic environmental conditions as well as regulatory limitation of spectrum access in unlicensed frequency bands, especially in the 2.4 GHz industrial, scientific and medical (ISM) band. In order to get these influences under control, a novel concept for an adaptive and low latency (≤ 1 ms) industrial wireless communications (IWC) system that adopts a robust IEEE 802.11p physical layer (PHY) is proposed and evaluated. Based on representative coexistence measurements in a real environment, the results of extensive simulations and analysis are shown in order to evaluate achievable latencies.
elib2cris::1512001600,kloc2016a

LSTM-DNN-Based Joint Wireless Signal Waveform Classification and Blind Transmitter Localization - Shatov, Victor; Shanin, Nikita; Perner, Bastian; Su, Yanpeng; Franchi, Norman; Lübke, Maximilian (International Symposium on Wireless Communication Systems (ISWCS), 2024)

Multi-Connectivity for Reliable Wireless Industrial Communications: Gains and Limitations - Mahdi, Ali H.; Hosler, Tom; Franchi, Norman; Fettweis, Gerhard (IEEE Wireless Communications and Networking Conference, WCNC, 2020)
Realizing wireless mission-critical applications in industry, such as closed-loop control, necessitates ultra-reliable low latency communications (URLLC) to achieve error-free message transmission with hard real-time requirements. Recently, multi-connectivity (MC) has been introduced as a promising scheme to ensure URLLC in Industry 4.0. However, implementing MC in mobile industrial communications rises multiple technical challenges, such as avoiding degradation in reliability due to fading and the shadowing effect, and managing multiple links in parallel which increases signaling overhead dramatically. To deal with these challenges, this paper investigates the gains and limitations of implementing MC in industrial wireless communications. It studies conflicting optimization problems using MC based on different radio parameters. Also, a link management scheme is introduced for MC to reduce the signaling overhead based on different radio parameters. The simulation results demonstrate gains and limitations of using MC and the selected parameters (frequency reuse factor, number of users, and frequency band) on the reliability and the signaling overhead in industrial communications.
CRIS-Team Scopus Importer:2021-06-08
Keywords: link management; maximum ratio combining; Multi-connectivity; network deployment; signaling overhead; URLLC

Multi-connectivity management for mobile ultra-reliable low-latency communications - Mahdi, Ali H.; Hößler, Tom; Scheuvens, Lucas; Franchi, Norman; Fettweis, Gerhard (WSA 2020 - 24th International ITG Workshop on Smart Antennas, 2020)
Recent mission critical wireless applications, such as emergency stop and safety application protocols (e.g., PROFIsafe), require ultra-reliable low-latency communications (URLLC) technologies to ensure error-free message transmission with hard real-time requirements. Multi-connectivity (MC) has emerged as a promising approach to enable URLLC in 5G. Applying MC in mobile communications poses multiple technical challenges, such as advanced handover (HO) schemes handling multiple links in parallel, highly dynamic link optimization, avoiding massive link drops due to fading and shadowing, and optimizing radio resource allocation/consumption. To address these challenges we propose an MC management scheme based on maximum ratio combining (MRC) for mobile communications in industrial scenarios. We compare the performance with existing HO schemes for Rayleigh fading channel conditions using extensive simulations. Compared to existing approaches, the results show improvements in achievable signal to noise ratio, link utilization, data rate, and availability.
CRIS-Team Scopus Importer:2021-06-08
Keywords: Handover; Link management; Maximum ratio combining; Multi-connectivity; URLLC

Multi-connectivity with joint decoding for 802.11bd under doubly-selective fading - Schwarzenberg, Nick; Jacob, Richard; Franchi, Norman; Fettweis, Gerhard (Proceedings of the 2020 27th International Conference on Telecommunications, ICT 2020, 2020)
Safety-critical driving applications such as emergency braking in a platoon require highly reliable low-latency communications. Since wireless data transmissions between vehicles are subject to fading radio channels, employing frequency diversity in terms of Multi-Connectivity (MC) is a promising approach to improve reliability under low latency constraints. Previous 802.11n link-level simulations of MC using Joint Decoding (JD) and Maximum Ratio Combining (MRC) as combining schemes indicate a growing performance margin of JD over MRC for more selective fading. In this work, we extend these investigations towards a doubly-selective highway channel model and the current draft of 802,llbd, Our results show the benefit of midamblebased channel estimation and indicate a significant advantage of MC over a single link and of JD over MRC in particular for achieving reliable vehicular communications.
CRIS-Team Scopus Importer:2021-06-08
Keywords: 802.11 bd; Diversity; Joint Decoding; Maximum Ratio Combining; Multi-Connectivity; Reliability; V2X; Vehicular

Network Planning and Coverage Optimization for Mobile Campus Networks - Krause, Anton; Anwar, Waqar; Martinez, Ana Belen; Stachorra, Dirk; Fettweis, Gerhard; Franchi, Norman (Proceedings - 2021 IEEE 4th 5G World Forum, 5GWF 2021, 2021)
The campus networks specified in 5G offer use-case tailored wireless communications that fulfills the demanding requirements of Industry 4.0 applications. Also agriculture and construction sites are fields of application that can benefit from the deployment of such networks. However, permanently installed campus networks do not match their requirements, as the network is needed only for certain time intervals and furthermore needs to be easily adaptable due to the time-varying nature of construction sites. Mobile campus networks (MCNs) solve this problem, as they can be deployed by a trailer in a short time and can be adjusted flexibly. Such MCNs require a very short and as much as possible automated planning and deployment procedure. Thus, conventional radio network planning (RNP) as it is applied for macro cells is too costly and time consuming, as it requires lots of manual effort and is not easily scalable. This paper presents an automated RNP framework for MCN based on MATLAB and WinProp, which optimizes the downlink coverage with one base station for several receiver heights that are relevant in an agricultural scenario. The proposed procedure also includes field measurements, which are intended to be executed by a drone. This allows a high flexibility in the selection of the measurement positions. An algorithm is developed that automates the environment-specific selection of measurement points and thus allows an efficient tuning of the propagation model. Subsequently, based on the measurements the propagation model is tuned and then used to recheck the results of the initial RNP. By applying another propagation model, real-world data are mimicked and the proposed algorithm is evaluated.
Created from Fastlane, Scopus look-up
Keywords: Dominant Path Model; Mobile Campus Networks; Model Tuning; Non-Public Networks; Radio Network Planning

NimbleNet: Serverless Computing for the Extreme Edge in Factory Environments - Müller, Kilian; Seidler, Maximilian; Ulbrich, Peter; Franchi, Norman (WoSC10 '24: Proceedings of the 10th International Workshop on Serverless Computing, 2024)
Modern factories are moving towards modular layouts with more generic production cells, allowing rapid production customization. Here, the cell's edge nodes exhibit considerable heterogeneity, ranging from simple microcontrollers to fully-fledged computing systems, which mandates that assembly-specific serverless functions used by Automated Guided Vehicles (AGVs) navigating through and linking the production cells are platform-independent. These moving manufacturing processes call for an adapted communication and distribution infrastructure to maintain low response times while minimizing network traffic. We present NimbleNet, a lightweight distribution and orchestration approach for serverless functions, specifically tailored for IoT devices in industrial factory settings. NimbleNet leverages lightweight sandboxing such as WebAssembly, dynamic dependency management, and a neighbor-first caching strategy to enable efficient, platform-independent deployment of tasks at the extreme edge. Our simulations and real-world evaluations demonstrate that our approach facilitates the dynamic deployment and execution of tasks on resource-constrained devices while optimizing the network load within a mesh network configuration.

Observer-Based Packet Drop Mitigation for String Stable CACC - Villamil, Andrés; González, Arturo; Franchi, Norman; Fettweis, Gerhard (ACM International Conference Proceeding Series, 2019)
This paper proposes a solution to increase the probability of a wirelessly interconnected platoon of vehicles being string stable under packet loss conditions without imposing additional requirements on the communications system. The string stability of a cooperative adaptive cruise control (CACC) is known to be achievable if no communication errors occur. However, this is an assumption hard to achieve, in particular for wireless communications. The proposed system consists of a CACC controller that switches between the signal transmitted from the previous vehicle (when available) and the estimated signal from an observer. This paper shows that the inclusion of an observer can improve the performance of the quality of control when packet losses are considered.
CRIS-Team Scopus Importer:2021-06-08
Keywords: CACC; hybrid systems; networked control system; observer; Platooning; string stability

On dependability metrics for wireless industrial communications-applied to IEEE 802.11ax - Trabl, Andreas; Scheuvens, Lucas; Hobler, Tom; Franchi, Norman; Fettweis, Gerhard P. (IEEE 5G World Forum, 5GWF 2019 - Conference Proceedings, 2019)
Wireless communications solutions allow to exchange data in a flexible and cheap manner, especially in industrial use cases, which experience an increasing attraction in the context of 5G. However, high demands towards latency and dependability, especially for closed-loop control purposes, still prevent the wide deployment in these scenarios. Studies on specific opportunities and limitations of potential technologies are still lacking. In this paper we present a simulative dependability analysis of the upcoming WLAN standard IEEE 802.11ax for industrial use cases. Small-scale fading as well as system noise are considered as error sources. State-of-the-art is a dependability analysis by means of packet error ratios. However, such a ratio is not able to reflect application demands precisely. Thus, in this paper a dependability analysis is carried out based on the recently proposed metrics reliability and availability. For applications able to handle a certain number of consecutive packet errors, two new metrics are proposed, i.e., application reliability and application availability. It is shown that applications utilizing closed-loop control can achieve a vast dependability gain when tolerating packet errors. The gain is higher in cases when bursts of packet errors occur rarely. We conclude that IEEE 802.11ax has a promising dependability for different applications for middle to high SNRs.
CRIS-Team Scopus Importer:2021-06-08
Keywords: Availability; Closed-loop control; IEEE 802.11ax; Industrial radio; Reliability; Wireless industrial communications

On Integrated Cooperative Radio Sensing for Spatial Electromagnetic Analysis in 6G - Shatov, Victor; Lübke, Maximilian; Su, Yanpeng; Franchi, Norman (2023 IEEE Future Networks World Forum (FNWF), 2023)

On network deployment for ultra-reliable communications using multi-connectivity - Mahdi, Ali H.; Kulkarni, Kedar; Franchi, Norman; Fettweis, Gerhard (IEEE Vehicular Technology Conference, 2019)
Mission-critical applications in future vehicular networks require highly reliable wireless communications. Multi-connectivity is a potential solution to meet the desired quality-of-services of these applications. In this work, we consider a highway scenario with multi-connectivity where a vehicle can combine packets transmitted by multiple remote-radio-heads. For given inter-site- distances, number of links, and frequency reuse factors, we derive the expression for outage probability considering communication links affected by shadowing. We investigate the effect of network deployment parameters on the achievable outage reliability under different radio parameters. The simulation results show trade-offs between inter-site distance and control parameters (frequency reuse factor and number of links), as well as network and radio channel parameters (number of satisfied users, effect of shadowing, and path loss exponent) on communications reliability.
CRIS-Team Scopus Importer:2021-06-08
Keywords: Frequency resuse; Inter-sitedistance; Multi-link diversity; Outage; Quality-of-service

On PHY Abstraction Modeling for IEEE 802.11ax based Multi-Connectivity Networks - Anwar, Waqar; Dev, Sourav; Kulkarni, Kedar; Franchi, Norman; Fettweis, Gerhard (IEEE Wireless Communications and Networking Conference, WCNC, 2019)
Emerging wireless communication use-cases demand ultra-reliable and low-latency communications. In order to meet these requirements, multi-connectivity (MC) approaches are being considered as a possible solution. To enable multi-connectivity with efficient use of resources, link adaptation requires not only to adopt modulation and coding scheme but also the number of links. This can be achieved by using an effective link quality metric (LQM) and mapping it to packet error rate or throughput, a process known as physical layer abstraction (PLA). In this paper, a new PLA method enhanced received bit information rate (eRBIR) is presented for OFDM based MC networks. The performance of proposed method is evaluated and compared against existing methods such as exponential effective SINR mapping (EESM) and received bit information rate (RBIR). Simulation results show that the proposed method enable an accurate and reliable link adaptation as compared to state of the art PLAs. Finally, the application of PLAs, to adapt the MCS in varying channel conditions is illustrated to ensure a certain target quality of service.
CRIS-Team Scopus Importer:2021-06-08
Keywords: Diversity Combining; EESM; IEEE 802.11ax; Link Adaptation; Multi-Connectivity; PHY Abstraction; RBIR

On the Detection of Vulnerable Road Users—Simulating Limits of an FMCW Radar - Yüksekkaya, Fatih; Franchi, Norman; Lübke, Maximilian (Electronics, 2024)
The complexity of urban traffic environments poses unique challenges for automotive radar sensors. Limited range and Doppler resolution hinder the ability to distinguish closely spaced objects and detect vulnerable road users, particularly pedestrians. Therefore, it is important to know the limits of FMCW radars. To assess these limitations, the WinProp channel simulator is used to model and simulate traffic scenarios regarding the detection of the range, velocity, and SNR of targets. To validate WinProp as a simulation tool for traffic scenarios, a real traffic scenario is configured and the simulation results compared to the measurement results in order to demonstrate the suitability of WinProp for simulating traffic scenarios and evaluating radar detection performance. The close agreement between the simulation and measurement results provides validation for WinProp’s accuracy in modeling detections and signal processing within traffic scenarios. To showcase the limitations of FMCW radars, two scenarios with challenging detection conditions are simulated: an occluded pedestrian between parked vehicles and a densely populated road. A monostatic setup with a single patch antenna and a 16 × 16 patch antenna array is evaluated, using chirp bandwidths of 1 GHz and 4 GHz. The simulations have shown that although it is feasible to detect an occluded pedestrian by multipath propagation, there is still a need in improving the detection performance when there is no multipath from an occluded pedestrian. Furthermore, the results indicate that higher bandwidth improves target separation but is insufficient for occluded pedestrian detection without multipath. However, with some targets, even the range resolution at 4 GHz was not sufficient, which required a separation in the Doppler dimension, emphasizing the need for overall resolution improvement of FMCW radars. Future work should focus on developing more complex road user models and simulating a broader range of scenarios to comprehensively evaluate radar performance in road traffic environments.<br
Keywords: FMCW radar; raytracing simulation; vulnerable road users

On the Reliability of NR-V2X and IEEE 802.11bd - Anwar, Waqar; Trasl, Andreas; Franchi, Norman; Fettweis, Gerhard (IEEE International Symposium on Personal, Indoor and Mobile Radio Communications, PIMRC, 2019)
Ultra-reliable communications enable various advanced use cases, such as autonomous driving and safety critical applications. However, state-of-the-art vehicular communications technologies, such as IEEE 802.11p and LTE-V2X, cannot meet the reliability requirement of all time-critical use cases. Therefore, the next generation of these technologies are being developed to enhance vehicular support for ultra-reliable use cases. In this paper, the reliability of these upcoming vehicular communications technologies (i.e., IEEE 802.11bd and NR-V2X) is analyzed. Even though physical layer standardizations are not yet available, proposed candidate settings are used for investigations. We use Monte Carlo simulations to evaluate the physical layer performance of these technologies in various vehicle-to-vehicle (V2V) scenarios. High Doppler shifts in V2V scenarios is one of the main challenges to enable ultra-reliable communications. It is shown that NR-V2X can be expected to outperform IEEE 802.11bd in terms of reliability due to better handling of Doppler shifts. In case of IEEE 802.11bd, high Doppler shifts cause packet errors even at high signal-to-noise ratios (SNRs). Therefore, different measures to improve the performance of IEEE 802.11bd are discussed and evaluated.
CRIS-Team Scopus Importer:2021-06-08
Keywords: IEEE 802.11bd; IEEE 802.11p; LTE-V2X; NR-V2X; ultra-reliable communications

Opportunistic 5G Spectrum Usage for Nomadic Ad-Hoc Emergency Communication - Horbach, Konrad; Perner, Bastian; Rehmann, Willi; Kretschmer, Mathias; Lübke, Maximilian; Rademacher, Michael; Franchi, Norman (2024 IEEE Future Networks World Forum (FNWF), 2024)

Optimized Measurement Location Planning for Interpolation-based Radio Environment Maps - Perner, Bastian; Franchi, Norman; Lübke, Maximilian (EUSIPCO, 2025)

Outage prediction for ultra-reliable low-latency communications in fast fading channels - Trassl, Andreas; Schmitt, Eva; Hoessler, Tom; Scheuvens, Lucas; Franchi, Norman; Schwarzenberg, Nick; Fettweis, Gerhard (EURASIP Journal on Wireless Communications and Networking, 2021)
The addition of redundancy is a promising solution to achieve a certain quality of service (QoS) for ultra-reliable low-latency communications (URLLC) in challenging fast fading scenarios. However, adding more and more redundancy to the transmission results in severely increased radio resource consumption. Monitoring and prediction of fast fading channels can serve as the foundation of advanced scheduling. By choosing suitable resources for transmission, the resource consumption is reduced while maintaining the QoS. In this article, we present outage prediction approaches for Rayleigh and Rician fading channels. Appropriate performance metrics are introduced to show the suitability for URLLC radio resource scheduling. Outage prediction in the Rayleigh fading case can be achieved by adding a threshold comparison to state-of-the-art fading prediction approaches. A line-of-sight (LOS) component estimator is introduced that enables outage prediction in LOS scenarios. Extensive simulations have shown that under realistic conditions, effective outage probabilities of 10 - 5 can be achieved while reaching up-state prediction probabilities of more than 90 %. We show that the predictor can be tuned to satisfy the desired trade-off between prediction reliability and utilizability of the link. This enables our predictor to be used in future scheduling strategies, which achieve the challenging QoS of URLLC with fewer required redundancy.
CRIS-Team Scopus Importer:2021-06-08
Keywords: Channel prediction; Radio resource scheduling; URLLC

Outage prediction for URLLC in rayleigh fading - Trasl, Andreas; Scheuvens, Lucas; Hosler, Tom; Schmitt, Eva; Franchi, Norman; Fettweis, Gerhard P. (2020 European Conference on Networks and Communications, EuCNC 2020, 2020)
A major challenge for the realization of ultra reliable low latency communications (URLLC) systems is the fast fading of wireless channels and the therewith associated outages. To overcome the fading, diversity concepts, as well as transmissions with low modulation order and low code rate are widely considered. However, these methods have an undeniably high resource consumption. In order to reduce it, fading prediction methods can be utilized as part of the scheduling strategy. We propose a novel outage prediction approach based on a Wiener filter that significantly helps to increase URLLC system monitoring and radio resource scheduling. In this paper we focus on Rayleigh fading channels and classical Doppler spectra. The proposed outage predictor is found to work on a wide range of sampling times and also with only a few observed fading samples available. During operation, future outage probabilities can be calculated beforehand and reliability guarantees can be made. Utilizing the proposed outage prediction method increases the achievable reliability of a link by several orders of magnitude compared to best effort transmissions on a single link. Links that are operable are well identified when little movement is present and prediction of several milliseconds is sufficient.
CRIS-Team Scopus Importer:2021-06-08
Keywords: Channel prediction; CQI aging; Radio resource scheduling; URLLC

Performance Analysis of Various Waveforms and Coding Schemes in V2X Communication Scenarios - Anwar, Waqar; Krause, Anton; Kumar, Atual; Franchi, Norman; Fettweis, Gerhard P. (IEEE Wireless Communications and Networking Conference, WCNC, 2020)
5G and beyond communications systems need to cope with a high degree of heterogeneity in terms of services and requirements. Specially, vehicle-to-everything (V2X) use cases require ultra-reliable and low latency communications (URLLC) under harsh channel conditions. To design an optimal waveform and coding scheme for such use cases is a key challenge. Therefore, new waveforms and coding techniques are need to be investigated. In this paper, we present a comparison of several waveform candidates (orthogonal frequency-division multiplexing (OFDM), discrete Fourier transform-spread-OFDM (DFT-s-OFDM), generalized frequency division multiplexing (GFDM) and orthogonal time frequency space (OTFS)) and coding schemes (convolution, turbo, low-density priority-check (LDPC) and polar) under a common framework. We consider two metrics, i.e. maximum data rates and packet error rate, to evaluate their performance under various fading conditions. The simulation results show that OTFS outperforms all other waveforms in both frequency selective and doubly selective channels. Regarding the coding schemes, turbo codes outperforms all other coding schemes, even though difference with LDPC codes is marginal.
CRIS-Team Scopus Importer:2021-06-08
Keywords: 5G and Beyond; Convolution Codes; DFT-s-OFDM; Fading channels; GFDM; LDPC Codes; OFDM; OTFS; Polar Codes; Turbo Codes; V2X

Performance analysis using physical layer abstraction modeling for 5G and beyond waveforms - Anwar, Waqar; Kumar, Atul; Franchi, Norman; Fettweis, Gerhard (2019 IEEE Global Communications Conference, GLOBECOM 2019 - Proceedings, 2019)
Physical layer abstraction (PLA) is commonly used in system level evaluations to speed up simulations. The accuracy of such evaluations highly depends on the modelling of PLA. Therefore, the main objective of this paper is to model and evaluate the performance of 5G and beyond (5GB) waveforms using PLA techniques. In the existing literature, PLA techniques were mainly used for orthogonal frequency division multiplexing (OFDM), which is commonly used to improve the performance under frequency selective fading. However, it suffers from high peak to average power ratio (PAPR). Therefore, to overcome this, DFT-spread- OFDM (DFT-s-OFDM) is used for uplink communication in the LTE/NR. In future use cases such as vehicle-to-everything (V2X), where high mobility is involved, inter-carrier interference becomes a bottleneck for above waveforms. Therefore, new waveforms are being proposed such as orthogonal time frequency space (OTFS). In the OTFS, data symbols are localized in delay-Doppler domain, and hence delay-Doppler channel impairments (due to mobility) can be easily compensated. To evaluate and compare the performance of above waveforms, we proposed waveforms specific PLA techniques. The proposed PLA techniques are validated though full PHY simulations, and used to compare the performance of different waveforms under frequency selective and doubly selective channels.
CRIS-Team Scopus Importer:2021-06-08
Keywords: DFT-s-OFDM; Link adaptation; OFDM; OTFS; PHY abstraction; System-level simulation

PHY Abstraction Techniques for IEEE 802.11p and LTE-V2V: Applications and Analysis - Anwar, Waqar; Kulkarni, Kedar; Augustin, Thomas R.; Franchi, Norman; Fettweis, Gerhard (2018 IEEE Globecom Workshops, GC Wkshps 2018 - Proceedings, 2019)
IEEE 802.11p and LTE-V2V are wireless standards of interest to enable connected and autonomous driving. To evaluate and compare the performance of these technologies under different channel conditions and reliability requirements, system level evaluations are required. For this purpose, we first present physical layer abstraction (PLA) techniques for IEEE 802.11p and LTE-V2V and then compare their performance using system level simulations. Using the proposed PLA methods, we compare the considered technologies in terms of throughput, latency and reliability. The results show that expected throughput, latency and packet error rate achieved by the proposed PLA methods are close to the bound obtained through full PHY simulations.
CRIS-Team Scopus Importer:2021-06-08
Keywords: Connected Vehicles; IEEE 802.11p; ITS; LTE-V2V; PHY abstraction; System-level simulation

PHY Abstraction Techniques for V2X Enabling Technologies: Modeling and Analysis - Anwar, Waqar; Dev, Sourav; Kumar, Atul; Franchi, Norman; Fettweis, Gerhard (IEEE Transactions on Vehicular Technology, 2021)
IEEE 802.11p and LTE-V2X are the current wireless standards of interest to enable connected and autonomous driving. The specification for their follow up generations, i.e., IEEE 802.11bd and NR-V2X are being developed and expected to be completed soon. To evaluate and compare the performance of these technologies, system-level studies are required to be carried out for various channel conditions and reliability requirements. However, these studies are time-intensive and require highly complex computations, if they are performed using link-level simulators. Therefore, the physical layer performance is usually abstracted using a link quality model, also known as Physical layer abstraction (PLA). For this purpose, we present novel PLA techniques to model different fading and interference effects for considered technologies. Further, we compare the performance of PLA techniques in terms of estimation accuracy against physical layer simulations. The results show that the estimated packet error rate (PER) by proposed PLA methods are close to the results obtained through physical layer simulations. Besides, we compare the performance of all considered technologies (i.e., IEEE 802.11p, LTE-V2X, IEEE 802.11bd, and NR-V2X) in terms of data rates, latency, and reliability. The results indicate that NR-V2X is superior in terms of average data rates compared to other technologies. In contrast, IEEE 802.11bd has lower transmission latency and higher reliability compared to other technologies.
CRIS-Team Scopus Importer:2021-06-08
Keywords: Connected vehicles; IEEE 802.11bd; IEEE 802.11p; LTE-V2X; NR-V2X; physical layer abstraction; system-level simulations

Physical Layer Abstraction for Multi-Connectivity Communications: Modeling and Analysis - Anwar, Waqar; Kumar, Atul; Franchi, Norman; Fettweis, Gerhard (IEEE Transactions on Wireless Communications, 2022)
The multi-connectivity is a key enabler for ultra-reliable low-latency communications. To evaluate its performance and suitability to various use cases system-level studies are essential, where the physical layer (PHY) plays an important role. Therefore, PHY modeling is required which is time-intensive and requires highly complex computations. For this purpose, the PHY performance is usually abstracted in terms of signal-to-interference-plus-noise ratio (SINR), also known as physical layer abstraction (PLA). However, due to fading, the symbols inside a packet could have different SINRs which require effective SINR mapping to compute an equivalent SINR. In the context of multi-connectivity, the received SINR depends on all connected links where each link experiences independent fading and on the used link combining technique. As a result, the computation of effective SINR also depends on the combining technique and fading experienced by individual links. To model PHY performance by considering all these effects, we develop PLA for multi-connectivity communications. This includes the computation of received symbols SINR for various link combining techniques and mapping them to effective SINR using enhanced exponential effective SINR mapping (eEESM). Furthermore, a new optimization method is introduced for eEESM to reduce its optimization complexity. Simulation results show that the proposed PLA accurately estimate the performance of different order of multi-connectivity communications under various fading conditions.<br

Physical Layer Abstraction for Ultra-Reliable Communications in 5G Multi-Connectivity Networks - Anwar, Waqar; Kulkarni, Kedar; Franchi, Norman; Fettweis, Gerhard (IEEE International Symposium on Personal, Indoor and Mobile Radio Communications, PIMRC, 2018)
The fifth generation (5G) of mobile communication will enable new use-cases such as self driving cars, smart automation and mission critical applications, which require ultra-reliable communications. Multi-Connectivity (MC) is a promising approach to achieve high reliability in wireless networks. In order to enable MC and efficiently utilize radio resources, dynamic link adaptation is required for choosing appropriate modulation schemes and number of links. This can be achieved by using an effective link quality metric such as effective signal-to-noise ratio (SNR) and mapping it to the packet error rate, a process referred to as physical layer abstraction (PLA). In this paper, we investigate and compare the performance of existing PLA methods especially exponential effective SNR mapping (EESM) and received bit information rate (RBIR), for OFDM-based MC systems. Furthermore, we propose a new robust PLA method, called enhanced EESM (eEESM). The eEESM minimizes the efforts of optimizing tuning parameter by fitting the variations in tuning parameter to known curves as a function of channel and diversity order. Simulation results show that eEESM outperforms the state of the art PLAs for different channel conditions, modulation and diversity orders.
CRIS-Team Scopus Importer:2021-06-08
Keywords: 5G; Diversity Combining; Dynamic Link Adaption; Multi-Connectivity; Physical Layer Abstraction; URLLC

Physical layer evaluation of V2X communications technologies: 5G NR-V2X, LTE-V2X, IEEE 802.11bd, and IEEE 802.11p - Anwar, Waqar; Franchi, Norman; Fettweis, Gerhard (IEEE Vehicular Technology Conference, 2019)
Vehicular communications and connected cars have an eminence potential to improve road safety and reduce the number of accidents by sharing information with their surrounding. The state of the art technologies to enable vehicular communications are IEEE 802.11p and LTE-V2X. A number of studies and field trials are carried out to evaluate their performance and suitability in various scenarios. On one hand 3GPP (3rd Generation Partnership Project) is working on the next generation V2X technology 5G NR-V2X to address new use cases and improve the performance. On the other hand, an IEEE 802.11 study group NGV (next generation V2X) is identifying new use cases and requirements to define a possible amendment IEEE 802.11bd. In this paper, we evaluate and compare the PHY layer performance of these upcoming technologies for vehicle-to-vehicle (V2V) communications. The purpose of this study is to identify which technology is more suitable for V2V communications. Our results show that NR-V2V is expected to outperform all other standards (even IEEE 802.11bd) in terms of reliability, range, latency and data rates. However, IEEE 802.11bd is expected to be more reliable with improved range and throughput compared to IEEE 802.11p.
CRIS-Team Scopus Importer:2021-06-08
Keywords: 5G NR; EMBB; IEEE 802.11 NGV; IEEE 802.11bd; IEEE 802.11p; ITS; LTE-V2X; NR-V2X; URLLC

Physical Layer Performance Modeling of Modern Multicarrier Modulation Techniques - Anwar, Waqar; Kumar, Atul; Franchi, Norman; Fettweis, Gerhard (IEEE Transactions on Communications, 2022)
The fifth-generation (5G) and beyond standards are being challenged by the diverse requirements of modern use cases. Multicarrier modulation techniques are one of the key components of the physical layer (PHY) design, which has immense potential to improve efficiency and reliability. In current state-of-the-art wireless technologies (i.e., NR and IEEE 802.11ax) orthogonal frequency division multiplexing (OFDM) is used which has many disadvantages such as peak-to-average power ratio (PAPR), out-of-band emission (OOBE), and sensitivity to carrier frequency offset (CFO). To overcome these drawbacks several alternate multicarrier modulation techniques are being considered, such as discrete Fourier transform-spread-OFDM (DFT-s-OFDM), generalized frequency division multiplexing (GFDM), and orthogonal time-frequency space (OTFS). In this paper, we develop the physical layer abstraction (PLA) of these candidate multicarrier techniques to evaluate their performance under various use cases and scenarios. The PLA is a commonly used technique to avoid time-consuming PHY simulations in system-level simulators. To improve the accuracy of PLA in different fading conditions, we derive a fitting parameter as a function of the received signal-to-interference-plus-noise ratio (SINR) variance. The validation results show that performance can be accurately estimated through the proposed multicarrier PLA. Moreover, PLA techniques are at least thousands of times faster compared to PHY simulations.<br
Keywords: Physical layer abstraction; system-level simulation; link adaptation; multicarrier modulation techniques; eEESM; EESM; RBIR; OFDM; DFT-s-OFDM; GFDM; OTFS

Position-Driven Wireless Multipath Channel Simulator for Square-Shaped Environments - Li, Zhongju; Bomfin, Roberto; Franco De Almeida, Ivo Bizon; Nimr, Ahmad; Franchi, Norman; Fettweis, Gerhard (2021 1st IEEE International Online Symposium on Joint Communications and Sensing, JC and S 2021, 2021)
In this paper, we propose an analysis of the wireless multipath channel in square-shaped environments. By considering propagation characteristics of the wireless transmission such as path-loss and reflections in this environment, we provide a wireless multipath channel generator that depends on transmitter and receiver position and can be easily integrated into numerical simulations. In order to demonstrate the validity of the proposed simulation framework, we provide a numerical analysis of the spatial channel correlation between two receivers over random positions of the transmitter in a defined area, which can be also treated as a performance indicator. Interestingly, the results show that the region where the transmitter is positioned has a large impact on the channel correlation. To corroborate our channel simulator, a blind energy detection based spectrum sensing has been implemented, where we show the influence of transmitter position and channel spatial correlation on the system performance.
CRIS-Team Scopus Importer:2021-06-08
Keywords: channel spatial correlation; Deterministic channel model; multi-path channel simulator; spectrum sensing

Predictive Algorithms for Communications-Control Co-Design in Multi-Robot Systems: Demonstrated with Two Drones in a Leader-Follower Setup - Seifaei, Zahra; Lübke, Maximilian; Franchi, Norman (EW24, 2025)
This paper investigates the joint design of communications and control systems for robots collaborating using Device to-Device connection. Factors like noise and interference in wireless channels can lead to data packet errors, potentially failing in task execution, and robot positioning. This paper addresses these challenges by proposing an outage probability model tailored explicitly for robotic engineers. This model empowers robots as receivers to decide about utilizing the received data. By analyzing the communications channel quality through the outage probability model, the receiver can assess the likelihood of errors and determine whether the data is reliable enough for the task. The model leverages Physical Layer Abstraction models for efficient simulations, and we demonstrate its application through a case study of two drones using a leader-follower approach. By tuning the model and selecting an optimal transmitting time, we minimize locational error at the receiver, crossing a balance between communications overhead and data reliability for improved task performance. As a result of these evaluations, an outage probability model was developed, which can be utilized at the receiver to perform reliable data transmission during the same leader-follower scenari
Keywords: Communications control co-design; D2D communication; leader-follower robotics; outage probability model; robotic collaboration

Private mobile ad hoc communications and the application in LANDNETZ - Hecker, Andreas; Striller, Benjamin; Franchi, Norman (LAND.TECHNIK 2022 The Forum for Agricultural Engineering Innovations, 2022)
Keywords: Electrical Agricultural Machines; GridCon2; tractor; scientific soil compaction; soil model; discrete element method; agricultural soil tillage; machine learning; macine adjustment; harvester; fleet performance; autonomous weed control; off-road and agricultural applications; fan-airflow adjustment; in-field-communication; alternative fuels; multifuel tractor

Project FAST-fast actuators sensors & transceivers - Ellinger, Frank; Meister, Tilo; Grosa, Patrick; Jamshidi, Kambiz; Ihle, David; Franchi, Norman; Wagner, Jens; Richter, Andreas; Fettweis, Gerhard; Fitzek, Frank H.P.; Kreissig, Martin; Klessig, Henrik; et al. (LAMC 2016 - IEEE MTT-S Latin America Microwave Conference, 2017)
In this paper we give an overview of the German project cluster FAST which targets a technical breakthrough by real-time with latencies below 1 ms to enable advanced applications in the area of connectivity, traffic, manufacturing and health. FAST is based on 25 technical projects conducted by over 80 partners in industry and research. The innovations are outlined and include high frequency communication aspects such as 20 Gb/s communications at 200 GHz, real-time OFDM MIMO imaging radar, real-time GPS navigation with < 1 m accuracy, encryption using the unique air channel between nodes, time-and scenario-dependent latency measurements, the mobile edge cloud concept as well as synchronization via Ethernet with achieved measured accuracy of 1 ns. Moreover, this paper aims at stimulating potential cooperation between Latin America and Germany.
CRIS-Team Scopus Importer:2021-06-08
Keywords: high speed communications; latency; real-time

Quantifying the Gain of Multi-Connectivity in Wireless LAN - Schwarzenberg, Nick; Wolf, Albrecht; Franchi, Norman; Fettweis, Gerhard (2018 European Conference on Networks and Communications, EuCNC 2018, 2018)
Multi-Connectivity (MC) using multi-link diversity is a promising approach to enable Ultra-Reliable Low-Latency Communications. While recent analytical results about MC already indicate improved reliability compared to a single link, we are interested in the actual gain of implementing MC into an established wireless standard. Therefore, we evaluate inter-frequency MC over independent fading channels for the physical layer of Wireless LAN (WLAN). We compare three combining schemes, namely Selection Combining (SC), Maximal Ratio Combining (MRC), and the recently emerging Joint Decoding (JD), by their respective packet error rates in Monte-Carlo simulations. Our results show that MC outperforms a single link for all of the three combining schemes, even if the total transmit power is not increased but shared among the available links. JD performs best and is found to be considerably less dependent on SNR estimation than MRC and SC. We show that packet synchronization in WLAN causes an error floor in frequency-selective channels which can be effectively mitigated by MC.
CRIS-Team Scopus Importer:2021-06-08
Keywords: Diversity Combining; Joint Decoding; Multi-Connectivity; URLLC; WLAN

Radio Hardware In-the-Loop Emulation for Testing Vehicular Communication Systems - Franchi, Norman; Fischer, Georg; Weigel, Robert (5th IEEE International Symposium on Wireless Vehicular Communications - VTC Spring 2013, 2013)
In this work, a novel test concept Radio Hardware In-the-Loop (RadioHIL) for next generation automotive electronic control units (ECUs) with wireless interfaces is proposed. The resulting test environment is well suited for ECUs networking with wireless sensors, actuators, mobile terminals or even with other vehicles and infrastructure elements. The presented RadioHIL approach is based on Software Defined Radio (SDR) architecture. The first step for executing the RadioHIL concept is the implementation of a multi-standard waveform design for automotive relevant purposes. Therefore the model-based implementations of two compliant IEEE 802.11b and 802.11p SDR transmitters are outlined, which are of interest for vehicular wireless communication. The emulation concept is demonstrated on the Universal Software Radio Peripheral (USRP) SDR platform.
elib2cris::1512001600,franchi2013b
Keywords: Software Defined Radio; Vehicular Wireless Communication; Wireless Automotive Sensor Networks; Hardware In-the-Loop; IEEE 802.11p; IEEE 802.11b; USRP; RadioHIL

Real-time Cooperative Spectrum Sensing: Reliable Localization of Unknown Interferers in Shared Spectrum - Kulkarni, Kedar; Franchi, Norman; Fettweis, Gerhard (SCC 2019 - 12th International ITG Conference on Systems, Communications and Coding, 2019)
Locating active users/transmitters and sources of spectral interference in real-time is a key challenge in next generation radio networks to enable robust wireless communication and highly dynamic radio resource allocation. We present and investigate a spectrum sensing network with multiple collaborating spectrum sensing units (SUs) which jointly find precise locations of active wireless transmitters in an observed area. The estimation of locations is based on measurements of received signal strength at SUs, taking into account that the measurements are perturbed by spatially correlated shadowing. We propose four localization methods for the cases of single and multiple active transmitters, namely, maximum likelihood search, generalized least squares, radio environment map (REM) based and compressed sensing based methods. The methods vary in their estimation accuracy and complexity. Simulation results present effects of various parameters on the localization performance and also show that there is no significant performance loss due to discretization.
CRIS-Team Scopus Importer:2021-06-08
Keywords: Localization; Maximum likelihood; Radio environment map; Spectrum sensing network

Real-Time Instance Segmentation for Parking Occupancy Detection Using CNNs - Lassen, Vincent; Lübke, Maximilian; Franchi, Norman (2025 IEEE Symposium on Computational Intelligence in Image, Signal Processing and Synthetic Media, 2025)

Reliable Real-time Localization and Tracking of Interferers Using Cooperative Spectrum Sensing - Kulkarni, Kedar; Franchi, Norman; Fettweis, Gerhard (IEEE Wireless Communications and Networking Conference, WCNC, 2019)
Locating active users/transmitters and predicting interference patterns in real-time is a key challenge in next generation radio networks to enable robust wireless communication and highly dynamic radio resource allocation. We consider a network of collaborating spectrum sensing units (SUs) and propose a two-phase approach for localization and tracking of transmitters using received signal strength at SUs. The first phase involves estimation of locations of multiple transmitters using compressed sensing based method. In the second phase, the location estimates are improved and velocities of mobile transmitters are estimated using extended Kalman filter. The proposed approach is evaluated through simulations considering an industrial channel model with correlated shadowing. We investigate the effect of SU placement, transmitter density, mobility and fading on the localization performance.
CRIS-Team Scopus Importer:2021-06-08
Keywords: compressed sensing; extended Kalman filter; Localization; spectrum sensing; tracking

Reliable wireless communication and positioning enabling mobile control and safety applications in industrial environments - Ehrig, Marcus; Petri, Markus; Sark, Vladica; Tesfay, Abraham Gebru; Melnyk, Sergiy; Schotten, Hans; Anwar, Waqar; Franchi, Norman; Fettweis, Gerhard; Marchenko, Nikolaj (Proceedings of the IEEE International Conference on Industrial Technology, 2017)
This paper introduces new functionalities for industrial safety applications using the wireless infrastructure of the IEEE 802.11 standard. The new amendments (n/ac/ad) for the 2.4, 5, and 60-GHz-band support additional high data rate modes, for e.g. video applications and device-to-device (D2D) communication. The huge bandwidth in the 60-GHz-band enables precise localization. However, Listen-Before-Talk (LBT) has to be used in order to guarantee fair channel access possibilities and coexistence of many devices. The access requirements are regulated (e.g. by ETSI for the European region). To cope with the uncertainty of coexistence and the special channel conditions in an industrial environment a multi-band PHY and MAC solution with multi-link-connectivity (MLC) support is introduced. This enables highly reliable low-latency wireless communication links for industrial safety applications. The simultaneous Round-Trip-Time-of-Flight (RTToF) ranging measurements enable position based features, like the introduced virtual safe zone.
CRIS-Team Scopus Importer:2021-06-08
Keywords: Communication; Industrial radio; Localization/positioning; Low-latency; MmWave; Mobility; Multi-band; Multi-link-connectivity; Parallel redundancy protocol; Quality of service; Reliability; Safety traffic; Seamless handover; ToF ranging; Wireless

Resilience-by-Design in 6G Networks: Literature Review and Novel Enabling Concepts - Khaloopour, Ladan; Su, Yanpeng; Raskob, Florian; Meuser, Tobias; Bless, Roland; Janzen, Leon; Abedi, Kamyar; Andjelkovic, Marko; Chaari, Hekma; Chakraborty, Pousali; Kreutzer, Michael; Hollick, Matthias; et al. (IEEE Access, 2024)
The sixth generation (6G) mobile communication networks are expected to intelligently integrate into various aspects of modern digital society, including smart cities, homes, health-care, transportation, and factories. While offering a multitude of services, it is likely that societies become increasingly reliant on 6G infrastructure. Any disruption to these digital services, whether due to human or technical failures, natural disasters, or terrorism, would significantly impact citizens' daily lives. Hence, 6G networks need not only to provide high-performance services but also to be resilient in maintaining essential services in the face of potentially unknown challenges. This paper provides a general review of the state of the art on resilient systems, definitions, concepts, and approaches. Moreover, it introduces a comprehensive concept, i.e., resilience-by-design (RBD), in three different levels for designing resilient 6G communication networks, summarizing our initial studies within the German Open6GHub project. First, we outline the general RBD enabling principles and discuss their related sub-categories. Next, adopting an interdisciplinary approach, we propose to embed these principles across all 6G layers/perspectives including electronics, physical channel, network components and functions, networks, services, and cross-layer and cross-infrastructure considerations and discuss their challenges. We further elaborate the RBD principles and their realizations along with several 6G use-cases. The paper is concluded by presenting a comprehensive list of open problems for future research on 6G resilience.
CRIS-Team Scopus Importer:2024-11-08
Keywords: 6G communication networks; attack; cross-layer design; dependability; failure; layerspecific design; resilience; resilience definitions; resilience enablers; resilience-by-design; security

RSS-based Localization of Multiple Unknown Transmitters through Particle Simulation - Schulz, Philipp; Franchi, Norman; Fettweis, Gerhard (2021 1st IEEE International Online Symposium on Joint Communications and Sensing, JC and S 2021, 2021)
The positions of wireless transmitters constitute valuable information for efficient dynamic radio resource planning, especially when resources are limited and communications is expected to be reliable and resilient. Moreover, in case there are unintended transmitters, i. e., jammers, the ability to localize them becomes even more important, in order to react and initiate appropriate countermeasures to finally recover operational mode. A joint design of transmitter sensing and radio resource utilization is of considerable benefit for dynamic network optimization especially in varying environments. In this paper, we propose a novel approach based on received signal strength (RSS) to iteratively localize one or multiple transmitters with a cooperative sensing network through particle simulation. By incorporating a transmit power estimation, the transmitters can be known or unknown. In particular, our RSS-based approach is widely independent from the specific wireless technology. Thereby, spatiotemporally correlated shadowing is considered. Our proposal is evaluated for accuracy and computation time considering a path loss model for an industrial scenario.
CRIS-Team Scopus Importer:2021-06-08
Keywords: Cooperative Spectrum Sensing; Localization; Received Signal Strength; Resilience

SDR-Proved Adaptive OFDM Guard Interval Scheme for Rapidly Varying Time-Dispersive Vehicular Broadcast Channels - Franchi, Norman; Kloc, Matej; Weigel, Robert (6th IEEE International Symposium on Wireless Vehicular Communications (WiVeC), 2014)
Driven by the results of existing field measurements for the characterization of vehicular radio channels, particularly vehicle-to-vehicle (V2V) channels, which showed that the effective range of possible maximum delay spreads is extremely wide (ranging from a few ns up to several μs), the strategic choice of Orthogonal Frequency Division Multiplexing (OFDM) with fixed guard interval (GI) duration shall be reconsidered at that point. Here, the major claims, both to optimize the data throughput at good channel conditions and to enable a reliable transmission of safety critical information at harsh environmental conditions, must be taken into account. Thus, in this paper, an adaptive guard interval (AGI) length scheme in context of vehicular ad hoc broadcast communication networks with rapidly time-varying channel conditions is proposed. The approach enables an OFDM symbol-based GI estimation without the prior knowledge of the GI length used in the transmitted symbol. By this means different GI lengths can be detected even within a frame. The suggested approach could be used to improve actual and upcoming physical layer (PHY) specifications, e.g. of Std. IEEE 802.11p. For a physically realistic evaluation of the proposed scheme, a fully IEEE 802.11p standard-compliant and reconfigurable softwaredefined radio (SDR) transmitter with symbol-based adaptable GI processing but fixed symbol duration is presented.
elib2cris::1512001600,franchi2014

Simulation Test System for Development and Testing of Electrical Drive Systems - Franchi, Norman; Wellmann, Sebastian (Vieweg+Teubner Verlag | Springer Fachmedien Wiesbaden GmbH, 2011)
The proposed approach focuses on the realization of a modular test stand concept for electrical drives that combines automated, high-quality and precise Hardware-in-the-Loop simulation testing with the development of the corresponding embedded control software. The real system under test consists of an electronic control unit, the corresponding electrical engine and a controllable dynamometer for dynamic load emulation.
elib2cris::1512001600,franchi2011
Keywords: Electrical Drives; Engine Test Stand; Hardware-in-the-Loop; Control Prototyping; Dynamic Load Emulation; Modular Design; Combined Development and Test Environment

SoK: A Taxonomy for Hardware-Based Fingerprinting in the Internet of Things - Spinnler, Christian; Labs, Torsten; Franchi, Norman (ARES '24: Proceedings of the 19th International Conference on Availability, Reliability and Security, 2024)
In IoT applications, embedded devices acquire and transmit data to control and optimize industrial processes. To trust this data, the data acquisition system, such as the sensors and the integrated signal processing components itself must be trusted. Approaches like hardware fingerprinting try to improve the overall security of such systems. In this paper, we review and systematize current research and trends in hardware fingerprinting. We provide insights to current research directions by reviewing multiple survey and review papers and derive a common definition for fingerprinting based on the reviewed literature. We identify three different fingerprinting techniques: hardware fingerprinting, behavior fingerprinting and radio frequency fingerprinting. By decomposing a generalized embedded system architecture, we provide four trust domains from which we can create a hardware fingerprint: main processing domain, on-device communication domain, peripheral domain and environmental domain. With the trust domains in place, a new fingerprinting taxonomy is developed, taking into account different data sources and evaluation techniques. We distinguish between intrinsic and extrinsic data sources and direct and indirect data evaluation. To understand the scope of fingerprinting techniques in terms of their trust domain and application scenarios, a new categorization model is created that ties the data sources to a physical asset of the device, making it possible to determine to what extend a device’s components can be trusted and in which applications it may be applicable.<br
Keywords: fingerprinting; embedded security; embedded systems; IoT; authentication

State-Aware Resource Allocation for Wireless Closed-Loop Control Based on Multi-Connectivity - Scheuvens, Lucas; Schulz, Philipp; Hossler, Tom; Franchi, Norman; Barreto, Andre; Fettweis, Gerhard P. (2020 IEEE Global Communications Conference, GLOBECOM 2020 - Proceedings, 2020)
Control communications co-design enables robust and scalable wireless closed-loop control system design. We study the metric 'control-communications availability' that allows consecutive errors until the control application is deemed dysfunctional. Multi-connectivity helps increasing the network availability, but there is a lack of dynamic and resource efficient link management. Thus, we propose the 'state-aware resource allocation' scheme, whereby parallel links can be assigned adaptively to a given connection, depending on the number of previously, consecutively lost packets. We develop a Markov chain that captures the novel resource allocation approach suited for closed-loop wireless control applications. Our approach outperforms static dual connectivity by two orders of magnitude in terms of control-communications availability while reducing the amount of required resources to approximately half.
CRIS-Team Scopus Importer:2021-06-08
Keywords: Adaptive Resource Management; Control Communications Co-Design; Control-Communications Availability; Multi-Connectivity; Wireless Control

State-Aware Resource Allocation for Wireless Closed-Loop Control Systems - Scheuvens, Lucas; Hoessler, Tom; Schulz, Philipp; Franchi, Norman; Barreto, Andre Noll; Fettweis, Gerhard P. (IEEE Transactions on Communications, 2021)
Wireless closed-loop control is of major significance for future industrial manufacturing. However, control applications pose stringent quality of service requirements for reliable operation. Contrary to traditional ultra-reliable low-latency communications design goals such as low packet loss rates and low latency, research results in the domain of networked control systems (NCS) state that depending on the sampling period, control applications inherently tolerate a few consecutive packet losses. This translates into a better-suited metric to capture control application requirements and therefore a more conclusive design goal for wireless networks: ensuring a maximum age of information (AoI). With a Markov modeling approach, we propose to exploit the tolerance through a novel dynamic multi-connectivity scheme that we term state-aware resource allocation (SARA), which temporally negatively correlates packet losses, thus avoiding long packet loss sequences. Through statistical multiplexing, SARA enables a mean time to failure (MTTF) in the order of years while keeping the per-agent average channel usage close to one, also in a multi-agent setting with competition for resources. Compared with static dual-connectivity, the MTTF can be increased 100-fold whereas the number of required channels reduces by 40%. Our approach also statistically guarantees system-wide AoI distributions, which aid to ensure control performance.
CRIS-Team Scopus Importer:2021-10-29
Keywords: adaptive resource management; age of information; availability; Control communications co-design; system analysis; wireless control

String stable CACC under LTE-V2V mode 3: Scheduling periods and transmission delays - Gonzalez, Arturo; Villamil, Andres; Franchi, Norman; Fettweis, Gerhard (IEEE 5G World Forum, 5GWF 2019 - Conference Proceedings, 2019)
A methodology for obtaining the LTE-V2V Mode 3 semi-persistent scheduling (SPS) period that fulfills the string stability condition in cooperative adaptive cruise control (CACC) is presented and validated for platoons with different vehicle types. Results show that the required SPS period depends on: the control loop parameters, the platoon kinematics, the relative ordering of the vehicles within the platoon and the communication parameters such as the modulation and coding scheme, the packet sizes and the number of assigned radio blocks.
CRIS-Team Scopus Importer:2021-06-08
Keywords: CACC; Communication requirements; LTE-V2V; Platooning; Semi-persistent scheduling; String stability

System analysis of state-aware resource allocation for closed-loop control systems - Scheuvens, Lucas; Schulz, Philipp; Hoßler, Tom; Franchi, Norman; Barreto, Andre; Fettwcis, Gerhard P. (2020 IEEE Global Communications Conference, GLOBECOM 2020 - Proceedings, 2020)
Wireless closed-loop control is of major significance for different application areas, such as future industrial manufacturing, and ultra-reliable low-latency communications (URLLC) are designed to enable such systems. Static multi-connectivity, in which a number of independent parallel channels are allocated for each service, is a possible solution to achieve URLLC requirements, but this increases resource usage significantly, which becomes an issue particularly in multi-user systems. Building upon a control-communications codesign (CoCoCo) approach, a control-application optimized state-aware resource allocation (SARA) scheme was developed, which exploits the control cycle's inherent capability of tolerating a limited number of consecutive packet losses before ultimately failing. In essence, SARA negatively correlates packet losses through dynamic channel allocation in order to yield extraordinary availability values while keeping the average resource consumption low. This article develops a multi-user system representation of SARA with competition for limited resources using a Markov chain approach and subsequently evaluates the mean time to failure, demonstrating that SARA scales better than static multi-connectivity, fully supporting the maximum system availability at fewer channels per agent.
CRIS-Team Scopus Importer:2021-06-08
Keywords: Adaptive Resource Management; Control Communications Co-Design; Multi-Connectivity; State-Aware Resource Allocation; System Analysis; Wireless Control

System-level performance comparison of IEEE 802.11p and 802.11bd draft in highway scenarios - Jacob, Richard; Anwar, Waqar; Schwarzenberg, Nick; Franchi, Norman; Fettweis, Gerhard (Proceedings of the 2020 27th International Conference on Telecommunications, ICT 2020, 2020)
Emerging applications such as cooperative automated driving in connection with technical advancements made in recent years require a new generation of V2X technologies. The upcoming IEEE 802.11bd standard, the successor of IEEE 802.11p, addresses increased throughput, range and reliability requirements by leveraging features such as high density midambles, dual carrier modulation and range extension. Within this work the authors present the first system-level evaluation of the upcoming standard. Therefore, a simulation framework to evaluate the transmission reliability in terms of packet reception ratio in highway scenarios with variable vehicle density is presented, based on which both technologies are compared. The results show significant improvements of the maximum transmission range, slight improvements in robustness against access layer packet loss and a strong performance degradation when using dual carrier modulation.
CRIS-Team Scopus Importer:2021-06-08
Keywords: DSRC; Dual carrier modulation; IEEE 802.11bd; IEEE 802.11p; ITS-G5; NGV; Range extension; Reliability; V2X

The significance of the Tactile Internet and 5G for digital agriculture - Franchi, Norman; Fettweis, Gerhard P.; Herlitzius, Thomas (at - Automatisierungstechnik, 2021)
The demand for internet access and data transfer is the key driver of mobile communications technologies. The next step is wireless real-time networking. The "Tactile Internet"demands completely new technologies. Low latency, short response times, high reliability and resilience, a network of edge clouds and security are basic requirements. Therefore, 5G is developed. Novel usecases are industrial automation, autonomous vehicles, e-health, and the Internet of Things. For agriculture, 5G is a crucial technology enabler for robotization and Smart Farming processes. Agriculture needs own ad-hoc radio network solutions to efficiently provide coverage and manage data transfer, privacy and flexibility. The synergy of cellular and local mesh communications can solve the problem of unreliable communication and allows farmers to take full control of their data.
CRIS-Team Scopus Importer:2021-06-08
Keywords: 5G; Smart Farming; Tactile Internet

TinyEP: TinyML-enhanced Energy Profiling for Extreme Edge Devices - Müller, Kilian; Weidner, Johannes; Franchi, Norman; Wägemann, Peter (IEEE Access, 2024)
The widespread integration of the Internet of Things (IoT) into daily operations has made optimizing energy consumption in low-power edge devices increasingly important. This is especially critical when battery-powered IoT platforms, like sensor networks, are provided to third parties to run custom sensing and perception applications. In such cases, two main requirements emerge: (A) accurate measurement of task energy consumption to fairly distribute maintenance and operations costs among parties and (B) reliable identification of tasks with high power consumption fluctuations to prevent interference with sensitive measurement campaigns. However, the need for compact, cost-effective, and energy-efficient power measurement solutions often compromises dynamic range, resolution, and overall measurement quality in these platforms. To address these challenges, we introduce TinyEP, a system that leverages machine learning on highly constrained microcontrollers (TinyML) to enhance the quality of power traces recorded by limited measurement hardware on highly constrained devices in real-time. Our approach incorporates online learning in the final layer of the model, combined with sparse feedback from an existing battery fuel gauge IC, to automatically adapt to new environments and compensate for concept drift. We evaluated the robustness of TinyEP under extreme conditions, demonstrating its effective operation within a temperature range of –40 °C to 80 °C. Our results show that TinyEP improves the Mean Absolute Percentage Error (MAPE) in recorded power traces and reduces the MAPE in task energy measurements from over 2% to under 0.8% across all tested scenarios. Additionally, it significantly decreases residual variance during task energy measurement

Using Probe Counts to Provide High-Resolution Detector Data for a Microscopic Traffic Simulation - Veihelmann, Christian Tobias; Shatov, Victor; Lübke, Maximilian; Franchi, Norman (Vehicles, 2024)

Wideband Aperture Coupled Patch Antenna for 6G Millimeter-Wave Applications - Sebastian, Caroline; Faghih-Naini, Samira; Reißland, Torsten; Weigel, Robert; Franchi, Norman; Scheiner, Benedict (2025 16th German Microwave Conference (GeMiC), 2025)